Antimicrobial nonwoven polyamide with zinc content

JP7629484B2Active Publication Date: 2025-02-13ASCEND PERFORMANCE MATERIALS OPERATIONS LLC
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2023096786
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-12-18
Filing Date
2023-06-13
Publication Date
2025-02-13
Estimated Expiration
2039-12-18

AI Technical Summary

Benefits of technology

【0011】 【0011】いくつかの実施形態では、本開示は、抗微生物性を有する不織ポリアミド、例えばナイロン66またはナイロン6/66構造であって、不織ポリアミド繊維を含み、繊維が、不織ポリアミド繊維内に分散した4000ppm未満の亜鉛、例えば3200ppm未満または3100ppm未満、および2000ppm未満のリンを含む、不織ポリアミド構造に関する。繊維は、25ミクロン未満、例えば20ミクロン未満の平均繊維直径を有する。ポリアミド構造は、ISO20743-13により測定して、Staphylococcus Aureusの少なくとも90%の減少を実証する。亜鉛対リンの重量比は、少なくとも1.3:1、または0.64未満:1であり得る。ポリアミド組成物の相対粘度は、100未満であり得る。構造および/または繊維は、リンの少なくとも一部を含むつや消し剤を含み得る。不織ポリアミドは、溶融紡糸、スパンボンド、電界紡糸、溶液紡糸または遠心紡糸され得る。いくつかのケースでは、20%以下の繊維は、700ナノメートル超の直径を有する。抗微生物繊維は、染浴テストにより測定して、70%超の亜鉛の保持率を有し得る。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007629484000008
    Figure 0007629484000008
  • Figure 0007629484000009
    Figure 0007629484000009
  • Figure 0007629484000010
    Figure 0007629484000010
Patent Text Reader

Abstract

To provide an antimicrobial fiber that maintains fiber strength and can be efficiently processed and ensures antimicrobial property after washing two or more times despite, for example, having low relative viscosity and / or using low die pressure.SOLUTION: A nonwoven polyamide structure having antimicrobial property includes a nonwoven polyamide fiber and the fiber includes zinc of less than 4000 ppm and phosphorus of less than 2000 ppm that are dispersed in the nonwoven polyamide fiber. The fiber has average fiber diameter of less than 25 micron. Reduction of at least 90% of Staphylococcus Aureus in the polyamide structure is demonstrated by measurement based on ISO20743-13.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0001] This application is related to and claims priority to U.S. Provisional Patent Application No. 62 / 781,233, filed December 18, 2018, which is incorporated herein by reference.

[0002]

[0002] The present disclosure relates to nonwoven polyamides having durable antimicrobial properties. In particular, the present disclosure relates to antimicrobial nonwoven polyamides that include a unique antimicrobial component. [Background technology]

[0003]

[0003] There is growing interest in fabrics with antimicrobial properties. In some instances, some treatments or coatings are applied to the fibers to provide antimicrobial properties to the fabric. Compounds containing copper, silver, gold or zinc have been used in these applications, either individually or in combination, to effectively combat pathogens such as bacteria, mold, mildew, viruses, spores and fungi.

[0004]

[0004] These types of antimicrobial fibers and fabrics can be used in many industries, including healthcare, hospitality, military, and athletics, among others. However, conventional antimicrobial fibers and fabrics have difficulty meeting many of the other requirements of these applications. Furthermore, many purportedly antimicrobial fabrics do not have sufficient antimicrobial properties, nor do these properties remain stable over the useful life of the product. In some instances, antimicrobial additives can have adverse environmental consequences by leaching out of the fabric.

[0005]

[0005] For example, in the healthcare and hospitality industries, certain fabrics are required to be hygienic at all times. To meet these hygiene standards, fabrics are routinely washed and often bleached. As another example, athletic clothing is susceptible to bacterial growth due to both internal and external factors, where sweat and bacteria transmitted through the skin can cause bacterial growth in the clothing fibers. In some cases, these bacteria cause unpleasant odors, stains, deterioration of the fabric, and even physical irritation, such as skin allergies and skin infections. Thus, repeated use and wash cycles are common in many applications. Unfortunately, conventional fabrics have been found to deteriorate and lose antimicrobial properties during repeated use and / or wash cycles.

[0006]

[0006] As an example of a conventional antimicrobial yarn and fabric, U.S. Patent No. 6,584,668 discloses a durable non-conductive metal treatment applied to the yarn and fabric. The durable non-conductive metal treatment is a coating or finish applied to the yarn and fabric. The metal treatment may include silver and / or silver ions, zinc, iron, copper, nickel, cobalt, aluminum, gold, manganese, magnesium, and the like. The metal treatment is applied as a coating or film to the outer surface of the yarn or fabric.

[0007]

[0007] Furthermore, U.S. Patent No. 4,701,518 discloses an antimicrobial nylon prepared in water with a zinc compound (ZnO) and a phosphorus compound to form carpet fibers. This process produces carpet nylon fibers having 18 denier per filament (dpf) and is prepared by conventional melt polymerization. Such carpet fibers typically have an average diameter well over 30 microns, which is generally not suitable for skin contact applications.

[0008]

[0008] Conventional polymer blends, such as the nylon blends mentioned above, are known to be difficult to process, especially in cases where fine fibers (and low denier) are desired, such as in nonwoven applications. Conventional blends, such as those containing nylon and various other additives, may require high die pressures to form small diameter fibers, which in turn may cause disadvantageous fiber breakage. In some cases, typical polymer blends have relative viscosities that are too high to process efficiently and may require adjustment, which can reduce overall efficiency. Summary of the Invention [Problem to be solved by the invention]

[0009]

[0009] While some references may teach the use of antimicrobial fibers and fabrics, there remains a need for antimicrobial fibers and fabrics that maintain fiber strength and ensure antimicrobial properties after multiple washes while still being efficient to process, e.g., having low relative viscosities and / or using low die pressures. [Means for solving the problem]

[0010]

[0010] According to some embodiments, the present disclosure relates to a nonwoven polyamide composition having permanent antimicrobial properties, comprising a nonwoven polyamide having an average fiber diameter of less than 25 microns, less than 2000 ppm zinc dispersed within the nonwoven polyamide, and less than 2000 ppm phosphorus, the weight ratio of zinc to phosphorus being at least 1.3:1, or less than 0.64:1. In some aspects, the weight ratio of zinc to phosphorus is at least 2:1. The relative viscosity of the polyamide composition can range from 10 to 100, such as from 20 to 100. In some aspects, the polyamide composition can include less than 500 ppm zinc. The polyamide composition can include a matting agent that includes at least a portion of the phosphorus. In some aspects, the polyamide composition is phosphorus-free. The zinc is obtained via zinc compounds including zinc oxide, zinc acetate, zinc ammonium carbonate, zinc ammonium adipate, zinc stearate, zinc phenylphosphinate, zinc pyrithione, and / or combinations thereof. In some embodiments, the zinc compound does not include zinc phenylphosphinate and / or zinc phenylphosphonate. In some embodiments, the phosphorus is obtained via phosphorus compounds including phosphoric acid, benzene phosphinic acid, benzene phosphonic acid, manganese hypophosphite, sodium hypophosphite, monosodium phosphate, hypophosphorous acid, phosphorous acid, and / or combinations thereof. In some embodiments, the polyamide composition includes less than 500 ppm zinc, the polyamide composition includes a matting agent that includes at least a portion of the phosphorus, and the polyamide composition is free of Staphylococcus cerevisiae as measured by ISO 20743-13. Aureus. In some embodiments, the polyamide comprises nylon, the zinc is obtained via zinc oxide and / or zinc pyrithione, and the relative viscosity of the polyamide composition ranges from 10 to 100, e.g., 20 to 100. In some embodiments, the polyamide comprises nylon-6,6, the zinc is obtained via zinc oxide, and the weight ratio of zinc to phosphorus is at least 2:1, and the polyamide composition demonstrates at least 90% reduction in Staphylococcus Aureus, as measured by ISO 20743-13. The nonwoven fabric may further comprise one or more additional antimicrobial agents, including silver, tin, copper, and gold, as well as alloys, oxides, and / or combinations thereof. The melting point of the nonwoven fabric may be 225° C. or higher. The nonwoven polyamide may be formed by melt, solution, centrifugation, or electrospinning. In some embodiments, the nonwoven polyamide has an average fiber diameter of 1000 nanometers or less. In some embodiments, no more than 20% of the fibers have a diameter greater than 700 nanometers. In some embodiments, the polyamide comprises nylon 66 or nylon 6 / 66. In some embodiments, the polyamide comprises high temperature nylon. In some embodiments, the polyamide comprises N6, N66, N6T / 66, N612, N6 / 66, N6I / 66, N66 / 6I / 6T, N11, and / or N12, where "N" refers to nylon. In some embodiments, the nonwoven polyamide has a ductility of 600 CFM / ft 2 In some embodiments, the nonwoven polyamide has an air permeability value of less than or equal to 200 GSM.

[0011] In some embodiments, the present disclosure relates to a nonwoven polyamide, such as nylon 66 or nylon 6 / 66 structure having antimicrobial properties, comprising nonwoven polyamide fibers, the fibers comprising less than 4000 ppm zinc, such as less than 3200 ppm or less than 3100 ppm, and less than 2000 ppm phosphorus dispersed within the nonwoven polyamide fibers. The fibers have an average fiber diameter of less than 25 microns, such as less than 20 microns. The polyamide structure demonstrates at least a 90% reduction in Staphylococcus Aureus, as measured by ISO 20743-13. The weight ratio of zinc to phosphorus may be at least 1.3:1, or less than 0.64:1. The relative viscosity of the polyamide composition may be less than 100. The structure and / or fibers may include a matting agent comprising at least a portion of the phosphorus. The nonwoven polyamide may be melt spun, spunbond, electrospun, solution spun, or centrifugally spun. In some cases, no more than 20% of the fibers have a diameter greater than 700 nanometers.The antimicrobial fibers may have greater than 70% zinc retention as measured by dye bath testing.

[0012] In some embodiments, the present disclosure relates to a method for preparing an antimicrobial nonwoven polyamide structure having permanent antimicrobial properties, comprising the steps of preparing a precursor polyamide optionally including an aqueous monomer solution, dispersing less than 4000 ppm zinc in the precursor polyamide, dispersing less than 2000 ppm phosphorus in the precursor polyamide, polymerizing the precursor polyamide to form a polyamide composition, spinning the polyamide composition to form an antimicrobial polyamide fiber, and forming the antimicrobial polyamide fiber into an antimicrobial nonwoven structure having a fiber diameter of less than 25 microns. The antimicrobial fiber may have greater than 70% zinc retention as measured by dye bath testing. The weight ratio of zinc to phosphorus may be at least 1.3:1, or less than 0.64:1. The polyamide may be melt spun by melt blowing through a die into a high velocity gaseous stream. The nonwoven polyamide may be melt spun, spunbonded, electrospun, solution spun, or centrifugally spun. The nonwoven fabric may include nylon 66 polyamide that is melt spun into fibers and formed into said nonwoven fabric, wherein no more than 20% of the fibers have a diameter greater than 25 microns.

[0013]

[0013] According to some embodiments, the present disclosure relates to an antimicrobial fiber having permanent antimicrobial properties, the antimicrobial fiber comprising a nonwoven polyamide having an average fiber diameter of less than 25 microns, less than 2000 ppm zinc dispersed within the nonwoven polyamide, and less than 2000 ppm phosphorus. In some aspects, the weight ratio of zinc to phosphorus is at least 1.3:1, or less than 0.64:1. In some aspects, the weight ratio of zinc to phosphorus is at least 2:1. In some aspects, the fiber has an average diameter of less than 20 microns. The nonwoven polyamide may comprise less than 500 ppm zinc. The nonwoven polyamide may comprise a matting agent comprising at least a portion of the phosphorus. The antimicrobial fiber may have a zinc retention of greater than 70% as measured by dye bath testing. The zinc may be a zinc compound including zinc oxide, zinc acetate, zinc ammonium carbonate, zinc ammonium adipate, zinc stearate, zinc phenylphosphinate, zinc pyrithione, and / or combinations thereof. The phosphorus may be a phosphorus compound including phosphoric acid, benzene phosphinic acid, benzene phosphonic acid, manganese hypophosphite, sodium hypophosphite, monosodium phosphate, hypophosphorous acid, phosphorous acid, and / or combinations thereof. The nonwoven polyamide may include less than 500 ppm zinc, the polymer includes a matting agent that includes at least a portion of the phosphorus, and the antimicrobial fiber demonstrates at least a 90% reduction in Staphylococcus Aureus as measured by ISO 20743-13. The nonwoven polyamide may include nylon, the zinc is provided in the form of zinc oxide and / or zinc pyrithione, and the polymer resin composition has a relative viscosity of 10 to 10. 0, e.g., 20 to 100, the antimicrobial fiber has a zinc retention of greater than 80% as measured by a dye bath test, and the fiber has an average diameter of less than 18 microns. The nonwoven polyamide may include nylon-6,6, the zinc is obtained in the form of zinc oxide, and the weight ratio of zinc to phosphorus is at least 2:1, the antimicrobial fiber demonstrates at least a 90% reduction in Staphylococcus Aureus as measured by ISO20743-13, the antimicrobial fiber has a zinc retention of greater than 95% as measured by a dye bath test, and the antimicrobial fiber has an average diameter of less than 10 microns. The nonwoven polyamide may further include one or more additional antimicrobial agents, including silver, tin, copper and gold, as well as alloys, oxides and / or combinations thereof. The melting point of the nonwoven fabric may be 225°C or higher. The nonwoven polyamide may be melt spun, spunbonded, electrospun, solution spun or centrifugally spun. In some embodiments, the nonwoven polyamide may have an average fiber diameter of 1000 nanometers or less. In some embodiments, no more than 20% of the fibers have a diameter greater than 700 nanometers. The polyamide may include nylon 66 or nylon 6 / 66. The polyamide may include high temperature nylon. The polyamide may include N6, N66, N6T / 66, N612, N6 / 66, N6I / 66, N66 / 6I / 6T, N11, and / or N12, where "N" refers to nylon. The nonwoven polyamide may have a fiber diameter of 600 CFM / ft 2 The nonwoven polyamide may have an air permeability value of less than 200 GSM. The nonwoven polyamide may have a basis weight of 200 GSM or less. Basis weight may be determined by ASTM D-3776 and is expressed in GSM (g / m 2 )

[0014]

[0014] According to some embodiments, the present disclosure relates to a method for preparing an antimicrobial nonwoven polyamide having permanent antimicrobial properties, comprising the steps of preparing an aqueous monomer solution for forming a polyamide, adding less than 1000 ppm zinc dispersed in the aqueous monomer solution, adding less than 2000 ppm phosphorus, polymerizing the aqueous monomer solution to form a polyamide, spinning the polyamide to form an antimicrobial polyamide fiber, and forming the antimicrobial polyamide fiber into an antimicrobial nonwoven polyamide having a fiber diameter of less than 25 microns, wherein the weight ratio of zinc to phosphorus is at least 1.3:1, or less than 0.64:1. The polyamide may contain less than 2000 ppm zinc. The antimicrobial fiber may have a zinc retention of greater than 70% as measured by a dye bath test. The step of adding phosphorus may include adding a matting agent comprising at least a portion of the phosphorus. The polyamide may be melt spun by melt blowing through a die into a high velocity gaseous stream. The polyamide may be melt spun by two-phase propellant gas spinning, which includes extruding a liquid polyamide composition through a fiber-forming channel with pressurized gas. The nonwoven fabric may be formed by collecting the fibers on a moving belt. In some embodiments, the relative viscosity of the polyamide in the nonwoven fabric may be reduced compared to the polyamide before spinning and forming the nonwoven fabric. In some embodiments, the relative viscosity of the polyamide in the nonwoven fabric is the same or increased compared to the polyamide before spinning and forming the nonwoven fabric. The nonwoven fabric may include nylon 66 polyamide that is melt spun and formed into said nonwoven fabric, the nonwoven fabric having a TDI of at least 20 ppm and an ODI of at least 1 ppm. The nonwoven fabric may include nylon 66 polyamide that is melt spun into fibers and formed into said nonwoven fabric, no more than 20% of the fibers having a diameter greater than 25 microns. In some embodiments, the polyamide is melt spun, spunbonded, electrospun, solution spun or centrifugally spun.

[0015] In some embodiments, the present disclosure relates to a nonwoven polyamide structure having antimicrobial properties, the nonwoven polyamide structure comprising nonwoven polyamide fibers having an average fiber diameter of less than 25 microns, less than 4000 ppm zinc dispersed within the nonwoven polyamide fibers. The polyamide composition is adapted to detect Staphylococcus A reduction of at least 90% of Aureus can be demonstrated.

[0016] In some embodiments, the present disclosure provides an antimicrobial nonwoven polyamide having antimicrobial properties. The present invention relates to a method for preparing an antimicrobial nonwoven structure comprising the steps of preparing a formulation comprising a polyamide, less than 4000 ppm zinc dispersed in the polyamide, and less than 2000 ppm phosphorus dispersed in the polyamide, spinning the formulation to form antimicrobial polyamide fibers having a fiber diameter of less than 25 microns, and forming the antimicrobial polyamide fibers into an antimicrobial nonwoven polyamide structure. The fibers may be spun using a die pressure of less than 275 psig.

[0017]

[0017] The present disclosure is described in detail below with reference to the drawings, in which like numerals designate similar parts. [Brief description of the drawings]

[0018] [Figure 1] 1 is a schematic diagram of an individual two-phase propellant gas spinning system useful in connection with the present disclosure. [Diagram 2] 1 is a schematic diagram of an individual two-phase propellant gas spinning system useful in connection with the present disclosure. [Diagram 3]

[0019] FIG. 1 is a micrograph at 50× magnification of nanofiber nylon 66 melt spun into a nonwoven fabric with an RV of 7.3. [Figure 4]

[0020] FIG. 4 is a photomicrograph at 8000× magnification of nanofibers of the grade of nylon 66 from FIG. 3 melt spun into a nonwoven fabric having an RV of 7.3. [Diagram 5]

[0021] FIG. 1 is a schematic diagram of a meltblowing process according to an embodiment of the present disclosure. [Figure 6]

[0022] FIG. 1 is a micrograph at 100× magnification of a nylon 66 nanofiber having 36 RVs. [Figure 7]

[0023] 1 is a graph comparing Thermal Degradation Index and Oxidative Degradation Index values ​​for nanofiber samples as a function of die temperature. [Figure 8]

[0024] 1 is a graph comparing Thermal Degradation Index and Oxidative Degradation Index values ​​for nanofiber samples as a function of meter pump speed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] Introduction

[0025] As discussed above, some conventional antimicrobial fibers and fabrics utilize antimicrobial compounds to inhibit pathogens. For example, some fabrics may contain antimicrobial additives, such as silver, that are applied to the outer layer as a film via topical treatment. However, these treatments have been found to often leach (rapidly) from the fabric. Similarly, in some non-coating applications where the antimicrobial additive is a component of the fiber, the antimicrobial additive is known to wash off, usually within about 10 wash cycles, leaching the additive into the environment.

[0020]

[0026] However, the disclosed nonwoven fibers and fabrics advantageously eliminate the need for topical treatments to make the antimicrobial agent in the garment. The antimicrobial fibers and fabrics have "built-in" antimicrobial properties. And, these properties advantageously do not wash off, even after significant washing or cleaning cycles. Additionally, the antimicrobial fibers can maintain colorfastness (a property relating to the resistance of a material to fading or bleeding) and durability. Unlike conventional antimicrobial fabrics, the fibers and fabrics do not lose antimicrobial activity through leaching and extraction, even after repeated use and cleaning cycles.

[0021]

[0027] Also, standards for carpet fibers relate to fibers / filaments of high denier (e.g., greater than 12 dpf) and / or large fiber diameter (e.g., greater than 20 microns). These carpet fibers are formed via completely different and dissimilar processes / equipment (filament spinning vs. fiber blowing), which results in completely different products (single long thick filament vs. multiple thin intertwined fibers). With regard to these significant differences, the teachings of such carpet fiber references are typically not consistent with those of, for example, nonwoven blowing. More specifically, in carpet fiber applications, formulations having different amounts, e.g., higher amounts of phosphorus compounds (optionally with zinc compounds), are used for their ability to increase the relative viscosity of the polymer.

[0022]

[0028] However, phosphorus compounds are typically not used in non-carpet, e.g., textile, polymer formulations, because their use and the associated relative viscosity increase can contribute to processability issues. In other words, non-woven equipment and processes cannot process carpet formulations (relative viscosity is increased) because the formulations can hinder processability, making them difficult, if not impossible, to produce. In contrast to carpet formulations, the (non-woven) polyamide compositions disclosed herein contain a unique combination of zinc, and optionally phosphorus, each preferably in specific, e.g., low amounts, that prevent or eliminate the viscosity increase associated with conventional carpet fiber formulations (and also provide additional synergistic benefits). As a result, the non-woven formulations disclosed herein are surprisingly capable of forming much finer fibers with antimicrobial properties, e.g., in the form of non-woven webs, without the aforementioned processing issues. Conventional formulations could not be efficiently spun into such small diameter fibers, e.g., nanofiber non-woven webs.

[0023]

[0029] Furthermore, conventional nylon formulations that utilize antimicrobial agents can require the use of high die pressures to form nonwoven mats of small diameter fibers. These high die pressures often cause detrimental fiber breakage.

[0024]

[0030] Also, some references directly mix antimicrobial agents with textiles, leather or plastics, but such processes did not solve the problem of product quality deterioration, as antimicrobial capabilities were lost due to thermal decomposition, loss of color fastness, or problems with leaching of the antimicrobial material. Still other conventional antimicrobial fabrics, such as nonwoven fabrics, have been found to have insufficient strength for clothing applications, such as being unable to withstand extensive washing and ensuring antimicrobial properties over the life of the product.

[0025]

[0031] Furthermore, it has now been discovered that the presence of zinc (zinc compounds), and optionally phosphorus, each preferably in a specific amount in the nonwoven polyamide composition, allows for the effective production of antimicrobial nonwoven fibers, such as nanofibers, capable of ensuring permanent antimicrobial properties. The production of these fibers can advantageously be achieved using operations at low die pressures. In some cases, the compositions have a lower relative viscosity (RV), which can contribute to operations at low die pressures. Without being bound by theory, in some embodiments, the use of phosphorus compounds in specific amounts allows the zinc to be more stably located in the polymer and / or fiber, and thus can prevent the zinc from leaching out of the fiber / fabric, for example during washing. In other words, the polyamide composition can have a certain amount of zinc and phosphorus embedded in the polyamide, so that they remain permanently antimicrobial. Furthermore, the use of nonwoven polyamides, especially nonwoven polyamides formed by melt spinning, solution spinning, centrifugal spinning or electrospinning processes, as polymer resins has been found to have improved durability. There are additional significant benefits to using the meltblown or spun nonwoven polyamides further described herein.

[0026]

[0032] Advantageously, it has also been found that providing a zinc compound and optionally a phosphorus compound to the polymer composition during the fiber production process, for example, in an aqueous monomer solution or via a masterbatch, produces fibers with antimicrobial agents evenly distributed throughout the fiber. In conventional processes, to provide antimicrobial properties to a fabric, a silver coating is applied to the outer surface of the fabric. However, the silver coating does not distribute throughout the fabric and is more susceptible to leaching of components, such as silver, into the environment. Advantageously, the polymer composition does not leach the antimicrobial agent and does not contain any toxic components, such as silver, and therefore does not cause toxicity. Furthermore, the polymer composition is characterized by the fact that it is not resistant to microbial agents and does not contain any toxic components, such as silver, and therefore does not cause toxicity. Antimicrobial fibers formed using the polymer composition do not require a separate application step since the antimicrobial agent is permanently disposed in the polymer and / or fiber.

[0027]

[0033] In other embodiments, the compositions contain little or no phosphorus. The disclosed zinc compounds, optionally in the disclosed amounts, impart beneficial properties to antimicrobial polyamide compositions and processes employing them, such as operating at low die pressures.

[0028]

[0034] As an added benefit, as discussed above, fibers formed using the nonwoven polyamide blends / compositions have advantageous physical characteristics, such as small average fiber diameter, which allows the fibers to be used in a variety of applications where larger fiber diameters are not preferred, such as clothing or other skin contact applications, as well as filtration, where larger fibers are not preferred.

[0029]

[0035] In one aspect, the disclosure relates to polyamide formulations / compositions that may be used in some cases to form antimicrobial fibers (nanofibers) that are optionally arranged to form a polyamide structure. The nonwoven polyamide compositions contain specific antimicrobial agents that are effective and highly resistant to washing or wear from the fiber. Importantly, the formulations provide processing advantages, such as the ability to form fine diameter fibers, be used to operate at low die pressures, and / or have favorable relative viscosity (RV) parameters. In one aspect, the antimicrobial fibers form a fabric or some part of a fabric. In some embodiments, the formulations include a polyamide or polyamide blend, and a zinc compound. In some cases, the formulations further include a phosphorus compound. Details of the components (and their compositional amounts), the articles formed therefrom, and their performance properties are disclosed herein.

[0030]

[0036] In some embodiments, the present disclosure relates to a non-woven polyamide structure, such as a mat, having antimicrobial properties. The structure comprises fine diameter polyamide fibers (in some cases non-woven fibers) having an average fiber diameter of, for example, less than 25 microns. The fibers comprise a zinc compound in a specific amount, and the zinc is dispersed within the fibers (as a component of the fiber / polymer), in contrast to conventional fibers or structures that may have an antimicrobial coating on their surface.

[0031]

[0037] The structure (and / or the fibers forming the structure) demonstrate improved antimicrobial performance, for example the structure demonstrates at least a 90%, such as at least a 99% reduction in Staphylococcus Aureus, or at least a 90%, such as at least a 99% reduction in Klebsiella pneumonia growth, as measured by ISO 20743-13. antimicrobial ingredients

[0038] As mentioned above, the polyamide formulation includes zinc and optionally phosphorus, preferably in specific amounts, in the polyamide composition to provide the aforementioned antimicrobial and / or physical / performance benefits. As used herein, "zinc compound" refers to a compound having at least one zinc molecule or ion. As used herein, "phosphorus compound" refers to a compound having at least one phosphorus molecule or ion.

[0032]

[0039] The polyamide compound (or structure or fiber made therefrom) includes zinc (a component), e.g., zinc is dispersed within the polyamide compound. In some embodiments, the concentration of zinc in the polyamide compound is from 100 ppb to 4000 ppm, e.g., from 500 ppb to 3500 ppm, from 1 ppm to 3500 ppm, from 200 ppm to 3000 ppm, from 275 ppm to 3100 ppm, from 200 ppm to 1500 ppm, from 100 ppm to 2000 ppm, from 200 ppm to 700 ppm, from 250 ppm to 550 ppm, from 1 ppm to 1000 ppm, e.g., from 25 ppm to 950 ppm, from 50 ppm to 900 ppm, from 100 ppm to 800 ppm, from 150 ppm to 700 ppm, from 175 ppm to 2000 ppm, from 250 ppm to 550 ppm, from 1 ppm to 1000 ppm ...2000 ppm, from 250 ppm to 2000 ppm, from 250 ppm to 2000 ppm, from 250 ppm to 2000 ppm, from 250 ppm to 2000 ppm, from 25 pm to 600 ppm, 200 ppm to 500 ppm, 215 ppm to 400 ppm, 225 ppm to 350 ppm, or 250 ppm to 300 ppm. In terms of the lower limit, the polyamide formulation contains more than 100 ppb zinc, e.g., more than 500 ppb, more than 1 ppm, more than 5 ppm, more than 10 ppm, more than 25 ppm, more than 50 ppm, more than 75 ppm, more than 100 ppm, more than 150 ppm, more than 175 ppm, more than 200 ppm, more than 215 ppm, more than 225 ppm, more than 250 ppm, or more than 275 ppm. In terms of upper limits, the polyamide formulation comprises less than 4000 ppm zinc, e.g., less than 3500 ppm, less than 3000 ppm, less than 3100 ppm, less than 2000 ppm, less than 1500 ppm zinc, less than 1000 ppm zinc, less than 950 ppm, less than 900 ppm, less than 800 ppm, less than 700 ppm, less than 600 ppm, less than 550 ppm, less than 500 ppm, less than 400 ppm, or less than 300 ppm zinc. In some embodiments, the zinc is embedded in a polymer formed from the polyamide formulation.

[0033]

[0040] The means by which zinc is provided to the polyamide formulation may vary widely. Many techniques for providing zinc in the polyamide formulation are contemplated by this disclosure and would be suitable. As an example, the zinc compound may be added as a component of the polyamide. In one embodiment, the zinc compound may be added as a masterbatch. The masterbatch may include a polyamide, such as nylon 6 or nylon 6,6. In yet another embodiment, the zinc compound may be added by sprinkling the powder onto the pellets. In yet another embodiment, the zinc may be added (as a powder) onto nylon 6,6 pellets and processed through a twin screw extruder to more evenly distribute the material in the polymer and improve additive uniformity throughout the fabric. In one embodiment, the zinc compound may be added to a salt solution during polyamide formation.

[0034]

[0041] In some embodiments, the formulation, structure and / or fiber includes phosphorus. Regardless of how phosphorus is obtained (see discussion below), phosphorus, like zinc, is present in the polyamide formulation. In some embodiments, the concentration of phosphorus in the polyamide formulation ranges from 10 ppm to 1000 ppm, for example, 20 ppm to 950 ppm, 30 to 900, 50 ppm to 850 ppm, 100 ppm to 800 ppm, 150 ppm to 750 ppm, 200 ppm to 600 ppm, 250 ppm to 550 ppm, 300 ppm to 500 ppm, or 350 ppm to 450 ppm. In terms of the upper limit, the concentration of phosphorus in the polyamide formulation may be less than 1000 ppm, e.g., less than 950 ppm, less than 900 ppm, less than 800 ppm, less than 700 ppm, less than 600 ppm, less than 500 ppm, less than 400 ppm, less than 300 ppm, or less than 200 ppm. In terms of the lower limit, the concentration of phosphorus in the polyamide formulation may be greater than 10 ppm, e.g., greater than 20 ppm, greater than 40 ppm, greater than 60 ppm, greater than 80 ppm, greater than 100 ppm, greater than 150 ppm, or greater than 180 ppm. In some embodiments, the phosphorus is embedded in the polymer of the polyamide formulation.

[0035]

[0042] The means by which phosphorus is provided to the polyamide formulation may vary widely. Many techniques for providing phosphorus to the polyamide formulation are contemplated by this disclosure and would be suitable. As an example, phosphorus or a phosphorus compound may be added as a component of the resin in a manner similar to that of, for example, zinc.

[0036]

[0043] In one embodiment, the phosphorus is provided as a component of another additive. For example, the phosphorus can be a component of a matting agent that is added to the polymer composition. Specifically, the phosphorus can be a coating additive / component of the matting agent. In some aspects, the matting agent comprises titanium dioxide. The titanium dioxide can comprise a phosphorus-containing surface coating, e.g., titanium dioxide coated with manganese. In some aspects, the phosphorus present in the polyamide composition is provided entirely by an additive, e.g., a matting agent. In some aspects, The phosphorus present in the polyamide composition is provided partly by the additive and partly as a phosphorus additive.

[0037]

[0044] In some aspects, the phosphorus present in the polyamide formulation is provided entirely by a matting agent, such as a titanium dioxide additive, and in the absence of phosphorus, for example, a phosphorus additive is added separately to the polyamide composition. For example, a titanium dioxide additive can be present in the polymer formulation, and the titanium dioxide contains less than 2000 ppm phosphorus based on the total weight of the polyamide formulation. In some embodiments, the polyamide formulation can include a titanium dioxide additive and a phosphorus additive, together providing less than 2000 ppm phosphorus based on the total weight of the polyamide formulation.

[0038]

[0045] In some embodiments, materials such as inorganic pigments may be utilized as matting agents. The matting agents may include one or more of titanium dioxide, barium sulfate, barium titanate, zinc titanate, magnesium titanate, calcium titanate, zinc oxide, zinc sulfide, lithopone, zirconium dioxide, calcium sulfate, barium sulfate, aluminum oxide, thorium oxide, magnesium oxide, silicon dioxide, talc, and mica. Coloring materials such as carbon black, copper phthalocyanine pigments, lead chromate, iron oxide, chromium oxide, and ultramarine blue may also be used. In some aspects, the matting agents include non-phenolic polycyclic compounds such as triphenylbenzene, diphenyl, substituted diphenyl, substituted naphthalene, and aromatic and polycyclic type chlorinated compounds such as diphenyl chloride.

[0039]

[0046] The inventors have found that in some cases, the use of a particular weight ratio of zinc to phosphorus minimizes the adverse effects of phosphorus on polyamide formulations, for example, too much phosphorus in a polyamide composition can cause polymer drip, increased polymer viscosity and inefficiencies in the production process.

[0040]

[0047] In one embodiment, the weight ratio of zinc to phosphorus in the polyamide formulation can be greater than 1.3:1, such as greater than 1.4:1, greater than 1.5:1, greater than 1.6:1, greater than 1.7:1, greater than 1.8:1, or greater than 2:1. In terms of ranges, the weight ratio of zinc to phosphorus in the polyamide formulation can range from 1.3:1 to 30:1, such as 1.4:1 to 25:1, 1.5:1 to 20:1, 1.6:1 to 15:1, 1.8:1 to 10:1, 2:1 to 8:1, 3:1 to 7:1, or 4:1 to 6:1. In terms of upper limits, the weight ratio of zinc to phosphorus in the polyamide composition can be less than 30:1, such as less than 28:1, less than 26:1, less than 24:1, less than 22:1, less than 20:1, or less than 15:1. In some aspects, there is no phosphorus in the polyamide formulation. In other embodiments, very low amounts of phosphorus are present. In some cases, the phosphorus is retained in the fiber / polymer along with the zinc.

[0041]

[0048] In one embodiment, the weight ratio of zinc to phosphorus in the polyamide formulation can be less than 0.64:1, such as less than 0.62:1, less than 0.6:1, such as less than 0.5:1, less than 0.45:1, less than 0.4:1, less than 0.3:1, or less than 0.25:1. In terms of ranges, the weight ratio of zinc to phosphorus in the polyamide formulation can range from 0.001:1 to 0.64:1, such as 0.01:1 to 0.6:1, 0.05:1 to 0.5:1, 0.1:1 to 0.45:1, 0.2:1 to 0.4:1, 0.25:1 to 0.35:1, or 0.2:1 to 0.3:1. In terms of the lower limit, the weight ratio of zinc to phosphorus in the polyamide formulation can be greater than 0.001:1, such as greater than 0.005:1, greater than 0.01:1, greater than 0.05:1, greater than 0.1:1, greater than 0.15:1, or greater than 0.2:1.

[0042]

[0049] In some cases, certain amounts of zinc and phosphorus can be used to enhance the properties of polyamide compounds, e.g. It has been determined that zinc and phosphorus can be mixed in finely divided form, e.g., in the form of granules, flakes, for example, into a polyamide resin composition to obtain a polyamide formulation which can then be formed into fibers, e.g., extruded or otherwise drawn, by conventional methods to produce fibers having substantially improved antimicrobial activity. Zinc and phosphorus are used in the polyamide formulation in the amounts described above to obtain fibers having permanent antimicrobial activity.

[0043]

[0050] As described herein, by utilizing polyamide formulations having the aforementioned zinc concentration, phosphorus concentration, and optionally relative viscosity ranges or other properties, the resulting antimicrobial fibers can secure a high percentage of zinc, and the resulting nonwoven fabric has (permanent or permanent) antimicrobial properties.

[0044]

[0051] In some embodiments, the antimicrobial fiber is formed from a polyamide formulation having a zinc retention of greater than 70%, e.g., greater than 75%, greater than 80%, greater than 90%, greater than 95%, or greater than 99%, as measured by dye bath testing. In terms of upper limits, the antimicrobial fiber has a zinc retention of less than 100%, e.g., less than 99.9%, less than 98%, less than 95%, or less than 90%. In terms of ranges, the antimicrobial fiber has a zinc retention in the range of 70% to 100%, e.g., 75% to 99.9%, 80% to 99%, or 90% to 98%.

[0045]

[0052] Zinc retention of fibers formed from polyamide formulations may be measured by dye bath testing, following a standard procedure: The sample is cleaned (all oils are removed) by a polishing process. The polishing process may use a heated bath carried out, for example, at 71° C. for 15 minutes. A polishing solution containing 0.25% Sterox (723 Soap) nonionic surfactant by weight of fiber ("owf") and 0.25% owf TSP (trisodium phosphate) may be used. The sample is then rinsed with water and then with cold water.

[0046]

[0053] The clarified sample may be tested according to the Chemical Dye Level Measurement Procedure. This procedure may involve placing the sample in a dye bath containing 1.0% owf CI Acid Blue 45, 4.0% owf MSP (monosodium phosphate) and sufficient % owf disodium phosphate or TSP to achieve a liquor to fiber ratio of 28:1 and a pH of 6.0. For example, if a pH below 6 is desired, a 10% solution of the desired acid may be added using an eye dropper until the desired pH is achieved. The dye bath may be preset to bring the bath to boiling at 100°C. The sample is placed in the bath for 1.5 hours. As an example, it may take approximately 30 minutes to reach boiling, and then the bath is held at boiling for 1 hour. The sample is then removed from the bath and rinsed. The sample is then transferred and centrifuged to extract the water. After the water is extracted, the sample is laid out and air dried. The amounts of the components before and after the procedure are then measured and recorded.

[0047]

[0054] In some embodiments, zinc is obtained as a zinc compound. The zinc compound may include zinc oxide, zinc acetate, zinc ammonium carbonate, zinc ammonium adipate, zinc stearate, zinc phenylphosphinate, zinc pyrithione, and combinations thereof. In some aspects, zinc is obtained in the form of zinc oxide. In some aspects, zinc is not obtained via zinc phenylphosphinate and / or zinc phenylphosphonate. Beneficially, the inventors have found that these particular zinc compounds work particularly well because they dissociate easily to form additional zinc ions.

[0048]

[0055] In some embodiments, the phosphorus is provided as a phosphorus compound. In an aspect, the phosphorus compound is phenylphosphinic acid, diphenylphosphinic acid, sodium phenylphosphinate, phosphorous acid, benzenephosphonic acid, calcium phenylphosphinate, potassium B-pentylphosphinate, methylphosphinic acid, manganese hypophosphite, sodium hypophosphite, The phosphorus compounds may include zinc, monosodium phosphate, hypophosphorous acid, dimethylphosphinic acid, ethylphosphinic acid, diethylphosphinic acid, magnesium ethylphosphinate, triphenyl phosphite, diphenylrnethyl phosphite, dimethylphenyl phosphite, ethyldiphenyl phosphite, phenylphosphonic acid, methylphosphonic acid, ethylphosphonic acid, potassium phenylphosphonate, sodium methylphosphonate, calcium ethylphosphonate, and combinations thereof. In some embodiments, the phosphorus compounds may include phosphoric acid, benzenephosphinic acid, benzenephosphonic acid, and combinations thereof. Phosphorus or phosphorus compounds may also be dispersed in the polymer along with zinc.

[0049]

[0056] In some embodiments, an antimicrobial agent, such as zinc, is added with phosphorus to promote incorporation of the antimicrobial agent into the fibers / polymers of the polyamide composition. This procedure advantageously allows the antimicrobial agent to be more uniformly distributed throughout the final fiber. Furthermore, this combination "builds in" the antimicrobial agent within the polyamide composition to help prevent or limit washing of the active antimicrobial ingredients from the fibers.

[0050]

[0057] In some embodiments, the polyamide composition may include an additional antimicrobial agent other than zinc. The additional antimicrobial agent may be in any suitable metal form, such as particulates, alloys and oxides, salts, such as sulfates, nitrates, acetates, citrates and chlorides, and / or ionic forms, such as silver, copper and / or gold. In some aspects, further additives, such as additional antimicrobial agents, are added to the polyamide composition. Antimicrobial performance

[0058] In some embodiments, the formulations, structures and / or fibers demonstrate improved antimicrobial performance, e.g., after 24 hours. For example, the formulations, structures and / or fibers may demonstrate at least a 90%, e.g., at least a 95%, at least a 99%, at least a 99.98, at least a 99.99, at least a 99.997, at least a 99.999 or at least a 99.9999 reduction (inhibition of growth) of Staphylococcus Aureus, as measured by ISO 20743-13.

[0051]

[0059] In some embodiments, the formulations, structures and / or fibers demonstrate improved antimicrobial performance, for example, the formulations, structures and / or fibers may demonstrate at least a 90%, e.g., at least a 95%, at least a 99%, at least a 99.98, at least a 99.99, at least a 99.999, at least a 99.9998 or at least a 99.9999 reduction (inhibition of growth) of Klebsiella pneumoniae as measured by ISO 20743-13.

[0052]

[0060] In terms of log reduction (Staphylococcus Aureus), the formulations, structures and / or fibers may demonstrate a log reduction of greater than 2.0, such as greater than 3.0, greater than 3.5, greater than 4.0, greater than 4.5, greater than 4.375, or greater than 5.0.

[0053]

[0061] In terms of log reduction (Klebsiella pneumoniae), the formulations, structures and / or fibers may demonstrate a log reduction of greater than 3.0, such as greater than 3.75, greater than 4.0, greater than 4.0, greater than 4.5, greater than 4.75, greater than 5.0, greater than 5.5, or greater than 6.0. Fiber size and distribution

[0062] The fibers disclosed herein can be microfibers, eg, fibers having an average fiber diameter of less than 25 microns, or nanofibers, eg, fibers having an average fiber diameter of less than 1000 nm (1 micron).

[0054]

[0063] In some embodiments, the fibers have an average fiber diameter less than the diameter of fibers formed for carpet-related applications that are generally not suitable for skin contact applications, e.g. For example, the fibers can have an average fiber diameter of less than 25 microns, e.g., less than 20 microns, less than 18 microns, less than 17 microns, less than 15 microns, less than 12 microns, less than 10 microns, less than 7 microns, less than 5 microns, less than 3 microns, or less than 2 microns.

[0055]

[0064] In some cases, the average fiber diameter of the nanofibers in the (fiber layer of the) nonwoven fabric may be less than 1 micron, e.g., less than 950 nanometers, less than 925 nanometers, less than 900 nanometers, less than 800 nanometers, less than 700 nanometers, less than 600 nanometers, or less than 500 nanometers. In terms of lower limits, the average fiber diameter of the nanofibers may be at least 100 nanometers, at least 110 nanometers, at least 115 nanometers, at least 120 nanometers, at least 125 nanometers, at least 130 nanometers, or at least 150 nanometers. In terms of ranges, the average fiber diameter of the nanofibers may be from 100 to 1000 nanometers, e.g., from 110 to 950 nanometers, from 115 to 925 nanometers, from 120 to 900 nanometers, from 125 to 800 nanometers, from 125 to 700 nanometers, from 130 to 600 nanometers, or from 150 to 500 nanometers. Such average fiber diameters allow nanofibers formed by the spinning methods disclosed herein to be distinguished from nanofibers formed by electrospinning methods. Electrospinning methods typically have average fiber diameters of less than 100 nanometers, such as from 50 to less than 100 nanometers. Without being bound by theory, it is believed that such small nanofiber diameters may cause reduced fiber strength and increased difficulty in handling the nanofibers. Nonetheless, several electrospinning methods may be envisioned.

[0056]

[0065] In some cases, the average fiber diameter of the microfibers in the nonwoven fabric may be less than 25 microns, e.g., less than 24 microns, less than 22 microns, less than 20 microns, less than 15 microns, less than 10 microns, or less than 5 microns. In terms of lower limits, the average fiber diameter of the microfibers in the nonwoven fabric may be at least 1 micron, at least 2 microns, at least 3 microns, at least 5 microns, at least 7 microns, or at least 10 microns. In terms of ranges, the average fiber diameter of the nanofibers in the fibrous layer of the nonwoven fabric may be 1 to 25 microns, e.g., 2 to 24 microns, 3 to 22 microns, 5 to 20 microns, 7 to 15 microns, 2 to 10 microns, or 1 to 5 microns. Such average fiber diameters distinguish the microfibers formed by the spinning methods disclosed herein from the fibers formed by the electrospinning methods.

[0057]

[0066] The use of the disclosed methods and formulations results in a specific and beneficial distribution of fiber diameters. For example, in the case of nanofibers, less than 20% of the nanofibers, such as less than 17.5%, less than 15%, less than 12.5%, or less than 10%, may have a fiber diameter from greater than 700 nanometers. In terms of lower limits, at least 1%, such as at least 2%, at least 3%, at least 4%, or at least 5% of the nanofibers have a fiber diameter greater than 700 nanometers. In terms of ranges, 1 to 20%, such as 2 to 17.5%, 3 to 15%, 4 to 12.5%, or 5 to 10% of the nanofibers have a fiber diameter greater than 700 nanometers. Such a distribution allows the nanofiber nonwoven products described herein to be distinguished from those formed by electrospinning, which has a small average diameter (50-100 nanometers) and a much narrower distribution, and those formed by non-nanofiber melt spinning, which has a much larger distribution. For example, centrifugally spun non-nanofiber nonwovens are disclosed in WO2017 / 214085, which reports fiber diameters from 2.08 to 4.4 microns, with a much broader distribution reported in Figure 10A of WO2017 / 214085, but electrospinning can still be used depending on the desired fiber diameter and distribution.

[0058]

[0067] In the case of microfibers, the fiber diameter may also desirably have a narrow distribution depending on the size of the microfiber. For example, less than 20% of the microfibers, such as less than 17.5%, less than 15%, less than 12.5%, or less than 10%, may have a fiber diameter of more than 2 microns above the average fiber diameter. In terms of lower limits, at least 1%, such as at least 2%, at least 3%, at least 4%, or at least 5% of the microfibers have a fiber diameter of more than 2 microns above the average fiber diameter. In terms of ranges, 1 to 20%, such as 2 to 17.5%, 3 to 15%, 4 to 12.5%, or 5 to 10% of the microfibers have a fiber diameter of more than 2 microns above the average fiber diameter. In further examples, the above-listed distributions may be within 1.5 microns, such as within 1.25 microns, within 1 micron, or within 500 nanometers of the average fiber diameter.

[0059]

[0068] In some embodiments, a combination of fibers having different average fiber diameters can be used. For example, a combination of nanofibers and microfibers can be used, such as a combination of fibers having an average fiber diameter of less than 1 micron and fibers having an average fiber diameter of 1 to 25 microns. In further embodiments, a combination of nanofibers having different average fiber diameters can be used. In yet further embodiments, a combination of microfibers having different fiber diameters can be used. In still further embodiments, a combination of 3, 4, 5 or more fibers having different fiber diameters can be used.

[0060]

[0069] In one embodiment, an advantage is anticipated to have two related polymers with different RV values ​​(both less than 330 and both with average fiber diameters less than 1 micron) blended for desired properties, such as increasing the melting point of the polyamide, tailoring the RV, or tailoring other properties.

[0061]

[0070] In one embodiment, an advantage is anticipated to have two related polymers with different RV values ​​(both less than 330 and with average fiber diameters as discussed herein) blended for desired properties, such as increasing the melting point of the polyamide, tailoring the RV, or tailoring other properties.

[0062]

[0071] Antimicrobial fibers and fabrics advantageously have durable antimicrobial properties. In some embodiments, the antimicrobial fibers may be formed from polyamides, polyesters, and blends thereof. The antimicrobial fibers may be spun to form nonwoven fabrics that provide advantageous antimicrobial properties to textiles, such as clothing, for example athletic apparel or other clothing that comes into contact with the skin.

[0063]

[0072] In some embodiments, the polyamide composition is used to produce antimicrobial molded and fabricated articles having permanent antimicrobial properties. In some aspects, molded and fabricated articles are produced that include the antimicrobial polyamide composition. In some aspects, the polyamide composition can further include additives, such as EBS and polyethylene wax, which are two non-limiting examples of additives.

[0064]

[0073] In some embodiments, the polyamide composition may be added directly into a plastic molding process prior to use in injection molding, extrusion, blow molding, or lamination processes, hi other embodiments, the polyamide composition may be added to form a masterbatch, which is then used to form a molded article.

[0065]

[0074] Some embodiments relate to molded and fabricated articles comprising the polyamide composition. In some aspects, the molded and fabricated articles are industrial products, various packaging materials, consumer products, or medical products, and the molded and fabricated articles are interior materials, such as blinds, wallpaper, and and flooring; food-related products, such as packaging films, storage containers and chopping boards; electrical appliances, such as humidifiers, cleaning machines and dishwashers; engineering materials, such as water and drainage pipes, and concrete; core materials in the medical field; and products for industrial purposes, such as coatings. The mouldings and fabrications are particularly useful for medical supplies, i.e. medical devices / products for insertion into the human body, such as catheters, prosthetics and bone repair materials for medical purposes or blood transfusion bags for medical purposes. Polyamide RVs, Compounds, Structures and Fibers

[0075] The RV of polyamides and formulations (and resulting structures and products) is generally the ratio of solution or solvent viscosities measured in a capillary viscometer at 25° C. (ASTM D 789) (2015). For this purpose, the solvent is 10% by weight water, and formic acid containing 90% by weight formic acid. The solution is 8.4% by weight polymer dissolved in the solvent.

[0066]

[0076] RV(η) used in relation to the disclosed polymers and products r ) is the ratio of the absolute viscosity of the polymer solution to the absolute viscosity of formic acid: η r =(η p / η f )=(f r ×d p ×t p ) / η f In the formula:d p = Density of formic acid-polymer solution at 25°C t p = average efflux time of the formic acid-polymer solution, η f = absolute viscosity of formic acid, kPa × s(E+6cP) and f r = viscometer tube coefficient, mm 2 / s(cSt) / s=η r / t3.

[0067]

[0077] Typical calculation for a 50RV specimen: ηr=(fr×dp×tp) / ηf During the ceremony: fr = Viscometer tube coefficient, typically 0.485675 cSt / s dp = density of polymer-formic acid solution, typically 1.1900 g / ml tp = average flow time of the polymer-formic acid solution, typically 135.00 s ηf = Absolute viscosity of formic acid, typically 1.56 cP This leads to an RV of ηr = (0.485675 cSt / s × 1.1900 g / ml × 135.00 s) / 1.56 cP = 50.0. The term t3 is the efflux time of the S-3 calibration oil used in determining the absolute viscosity of formic acid as required by ASTM D789 (2015).

[0068]

[0078] Advantageously, it has been discovered that the addition of zinc and optionally phosphorus in excess of the ratios identified above can result in beneficial relative viscosities of polyamide compounds, structures and / or fibers. In some embodiments, the RV ranges from 1 to 100, such as 10 to 100, 20 to 100, 25 to 80, 30 to 60, 40 to 50, 1 to 40, 10 to 30, 15 to 20, 20 to 35 or 25 to 32. In terms of the lower limit, the RV can be greater than 1, such as greater than 10, greater than 15, greater than 20, greater than 25, greater than 30, greater than 35, or greater than 40. In terms of the upper limit, the RV can be less than 100, such as less than 80, less than 60, less than 40, less than 35, less than 32, less than 30, or less than 20.

[0069]

[0079] In some embodiments, the RV of the (precursor) polyamide has a lower limit of at least 2, e.g., at least 3, at least 4 or at least 5. In terms of upper limits, the polyamide has a RV of 330 or less, 300 or less, 275 or less, 250 or less, 225 or less, 200 or less, 150 or less, 100 or less or 60 or less. In terms of ranges, the polyamide may have an RV of 2 to 330, e.g., 2 to 300, 2 to 275, 2 to 250, 2 to 225, 2 to 200, 2 to 100, 2 to 60, 2 to 50, 2 to 40, 10 to 40 or 15 to 40, and any value therebetween.

[0070]

[0080] In some embodiments, the RVs of the nonwoven structure are at least 2, e.g., at least In terms of upper limits, the nanofiber nonwoven product has an RV of 330 or less, 300 or less, 275 or less, 250 or less, 225 or less, 200 or less, 150 or less, 100 or less, or 60 or less. In terms of ranges, the nonwoven can have an RV of 2 to 330, e.g., 2 to 300, 2 to 275, 2 to 250, 2 to 225, 2 to 200, 2 to 100, 2 to 60, 2 to 50, 2 to 40, 10 to 40, or 15 to 40, and any value therebetween.

[0071]

[0081] The relationship between the RV of the (precursor) polyamide composition and the RV of the nonwoven structure or fibers thereof may be varied. In some embodiments, the RV of the nonwoven fabric may be lower than the RV of the polyamide composition. Lowering the RV has not traditionally been a desirable practice when spinning nylon 66. However, the inventors have discovered that this is advantageous in the production of microfibers and nanofibers. It has been unexpectedly discovered that the use of low RV polyamide nylons, such as low RV nylon 66, in melt spinning processes results in microfiber and nanofiber filaments with unexpectedly small filament diameters.

[0072]

[0082] The method of lowering the RV may vary widely. In some cases, the temperature of the process may be increased to lower the RV. However, in some embodiments, increasing the temperature may only slightly lower the RV, since the temperature affects the kinetics of the reaction but not the reaction equilibrium constant. The inventors have found that, beneficially, the RV of polyamides, such as nylon 66, can be lowered by adding moisture to depolymerize the polymer. Up to 5%, such as up to 4%, up to 3%, up to 2% or up to 1% moisture may be included before the polyamide begins to hydrolyze. This technique offers unexpected advantages over the traditional method of adding other polymers, such as polypropylene, to polyamides (to lower the RV).

[0073]

[0083] In some embodiments, RV can be adjusted, for example, by lowering temperature, manipulating zinc amount, and / or reducing moisture. Also, temperature has a relatively modest effect on adjusting RV compared to moisture content. Moisture content can be reduced to as low as 1 ppm or more, for example 5 ppm or more, 10 ppm or more, 100 ppm or more, 500 ppm or more, 1000 ppm or more, or 2500 ppm or more. Reducing moisture content is also favorable for reducing TDI and ODI values, which are discussed further herein. The inclusion of a catalyst can affect kinetics, but not the actual equilibrium constant.

[0074]

[0084] In some embodiments, the RV of the nonwoven is at least 20% lower than the RV of the polyamide before spinning, e.g., at least 25% lower, at least 30% lower, at least 35% lower, at least 40% lower, at least 45% lower, or at least 90% lower.

[0075]

[0085] In other embodiments, the RV of the nonwoven is at least 5% higher than the RV of the polyamide before spinning, e.g., at least 10% higher, at least 15% higher, at least 20% higher, at least 25% higher, at least 30% higher, or at least 35% higher.

[0076]

[0086] In still further embodiments, the RV of the polyamide and the RV of the nonwoven may be substantially the same, for example, within 5% of each other.

[0087] Additional embodiments of the present disclosure involve the production of antimicrobial structures comprising polyamide nanofibers and / or microfibers having an average fiber diameter of less than 25 microns and having an RV of 2 to 330. In this alternative embodiment, preferred RV ranges include 2 to 330, e.g., 2 to 300, 2 to 275, 2 to 250, 2 to 225, 2 to 200, 2 to 100, 2 to 60, 2 to 50, 2 to 40, 10 to 40, or 15 to 40. The nanofibers and / or microfibers are then converted into a nonwoven web. As the RV increases beyond about 10 to 30, e.g., 20 to 30, the operating temperature becomes a larger parameter to consider. At RVs above the range of about 10 to 30, e.g., 20 to 30, the temperature must be carefully controlled so that the polymer melts for processing purposes. Methods or examples of melting techniques, as well as heating and cooling sources that can be used in the apparatus to independently control the temperature of the fiber generating device, are described in U.S. Pat. No. 8,777,599, which is incorporated herein by reference. Non-limiting examples include resistive heaters, radiative heaters, cooling or heating gases (air or nitrogen), or conductive, convective, or radiative heat transfer mechanisms. Non-woven polyamide properties

[0088] The spinning process described herein can produce antimicrobial nonwoven polyamide structures (and fibers) with relatively low Oxidative Degradation Index ("ODI") values. A low ODI indicates less severe oxidative degradation during manufacture. In some embodiments, the ODI can range from 10 to 150 ppm. The ODI can be measured using gel permeation chromatography (GPC) with a fluorescence detector. The instrument is calibrated with an external standard of quinine. 0.1 grams of nylon is dissolved in 10 mL of 90% formic acid. The solution is then analyzed by GPC with a fluorescence detector. The detector wavelengths for ODI are 340 nm for excitation and 415 nm for emission. In terms of upper limits, the ODI of the antimicrobial nonwoven polyamide can be 200 ppm or less, for example 180 ppm or less, 150 ppm or less, 125 ppm or less, 100 ppm or less, 75 ppm or less, 60 ppm or less, or 50 ppm or less. In terms of lower limits, the ODI of the antimicrobial nonwoven polyamide can be 1 ppm or more, 5 ppm or more, 10 ppm or more, 15 ppm or more, 20 ppm or more, or 25 ppm or more. In terms of ranges, the ODI of the antimicrobial nonwoven polyamide can be 1 to 200 ppm, 1 to 180 ppm, 1 to 150 ppm, 5 to 125 ppm, 10 to 100 ppm, 1 to 75 ppm, 5 to 60 ppm, or 5 to 50 ppm.

[0077]

[0089] In addition, the spinning process described herein can result in a relatively low thermal degradation index ("TDI"). A low TDI indicates that the thermal history of the polyamide during production is not too severe. TDI is measured in the same way as ODI, except that the wavelength of the TDI detector is 300 nm for excitation and 338 nm for emission. In terms of the upper limit, the TDI of the polyamide nanofiber nonwoven fabric can be 4000 ppm or less, such as 3500 ppm or less, 3100 ppm or less, 2500 ppm or less, 2000 ppm or less, 1000 ppm or less, 750 ppm or less, or 700 ppm or less. In terms of the lower limit, the TDI of the polyamide nanofiber nonwoven fabric can be 20 ppm or more, 100 ppm or more, 125 ppm or more, 150 ppm or more, 175 ppm or more, 200 ppm or more, or 210 ppm or more. In terms of ranges, the TDI of the polyamide nanofiber nonwoven fabric can be 20 to 400 ppm, 100 to 4000 ppm, 125 to 3500 ppm, 150 to 3100 ppm, 175 to 2500 ppm, 200 to 2000 ppm, 210 to 1000 ppm, 200 to 750 ppm, or 200 to 700 ppm.

[0078]

[0090] TDI and ODI test methods are also disclosed in US Patent No. 5,411,710. A low TDI and / or ODI value is beneficial because it indicates that the antimicrobial nonwoven polyamide is more durable than a product with a high TDI and / or ODI. As explained above, TDI and ODI are measurements of degradation, and a product with high degradation may not function properly. For example, such a product may have inconsistent dye uptake, low thermal stability, short life in filtration applications where the fiber is exposed to heat, pressure, oxygen, or any combination thereof, and lower toughness in industrial fiber applications.

[0079]

[0091] One possible method that can be used to form antimicrobial nonwoven polyamides with low TDI and / or ODI is to include the additives described herein, particularly antioxidants. Such antioxidants are not essential to the conventional process, but may be used to inhibit degradation. Examples of useful antioxidants include copper halides and Nylostab® S-EED® available from Clariant.

[0080]

[0092] The spinning process described herein is capable of producing 600 CFM / ft 2 Less than, for example, 590 CFM / ft 2 Less than 580 CFM / ft 2 Less than 570 CFM / ft 2 Less than 560 CFM / ft 2 Less than or equal to 550 CFM / ft 2 This can also result in an antimicrobial nonwoven polyamide structure (or fiber) having an air permeability value of less than 50 CFM / ft. 2 , at least 75 CFM / ft 2 , at least 100 CFM / ft 2 , at least 125 CFM / ft 2 , at least 150 CFM / ft 2 or at least 200 CFM / ft 2 In terms of range, the antimicrobial nonwoven polyamide may have an air permeability value of 50 to 600 CFM / ft 2 , 75 to 590 CFM / ft 2 , 100 to 580 CFM / ft 2 , 125 to 570 CFM / ft 2 , 150 to 560 CFM / ft 2 or 200 to 550 CFM / ft 2 The air permeability value may be

[0081]

[0093] The spinning method described herein can also result in antimicrobial nonwoven polyamides with a filtration efficiency of 1 to 99.999%, for example 1 to 95%, 1 to 90%, 1.5 to 85% or 2 to 80%, as measured by a TSI 3160 automatic filter tester. The TSI 3160 automatic filter tester is used to test the efficiency of the filter material. Particle penetration and pressure drop are two important parameters measured using this instrument. Efficiency is 100%-Penetration. A challenge solution with a known particle size is used. The TSI 3160 is used to measure Hepa filters and DOP solutions. It combines an electrostatic classifier with a dual condensation particle counter (CPC) to measure maximum penetration particle size (MPPS) from 15 to 800 nm using monodisperse particles, and can test efficiencies up to 99.999999%. compound

[0094] In one embodiment, the formulation, structure and / or fiber comprises less than 3100 ppm zinc, and a matting agent comprising at least a portion of phosphorus, and can demonstrate at least a 95% reduction in Staphylococcus Aureus as measured by ISO 20743-13.

[0082]

[0095] In one embodiment, the formulation, structure and / or fiber comprises 275 ppm to 3100 ppm zinc, little or no phosphorus, and the polyamide nylon-6,6 may have an average fiber diameter of less than 1 micron, and may demonstrate at least a 95% reduction in Staphylococcus Aureus and at least a 99% reduction in Klebsiella pneumonia as measured by ISO 20743-13.

[0083]

[0096] In one embodiment, the formulation, structure and / or fiber contains less than 3100 ppm zinc, little or no phosphorus, and the polyamide nylon-6,6 may have an average fiber diameter of less than 1 micron, and may demonstrate at least a 95% reduction in Staphylococcus Aureus and at least a 99% reduction in Klebsiella pneumonia as measured by ISO 20743-13.

[0084]

[0097] In one embodiment, the formulation, structure and / or fiber may contain 200 to 1500 ppm zinc (optionally obtained as zinc oxide and / or zinc stearate), little or no phosphorus, may have a RV ranging from 10 to 30, may have an average fiber diameter of less than 1 micron, may demonstrate at least a 99% reduction in Staphylococcus Aureus as measured by ISO 20743-13, and may be resistant to at least a 99% reduction in Staphylococcus Aureus as measured by Klebsiel A reduction of at least 99.9% in la pneumonia can be demonstrated.

[0085]

[0098] In another embodiment, the polymer comprises a nylon-based polymer, the zinc is obtained via zinc oxide and / or zinc pyrithione, and the relative viscosity of the polyamide composition ranges from 10 to 100, such as from 20 to 100.

[0086]

[0099] In yet another embodiment, the polymer comprises nylon-6,6, the zinc is obtained via zinc oxide, and the weight ratio of zinc to phosphorus is at least 2:1, and the polyamide composition may demonstrate at least a 95% reduction in Staphylococcus Aureus as measured by ISO 20743-13.

[0087]

[0100] In one embodiment, the antimicrobial fiber contains at least 500 ppm of zinc, phosphorus, The antimicrobial fibers, which include a polymer containing a matting agent, also demonstrate at least a 90% reduction in Staphylococcus Aureus.

[0088]

[0101] In another embodiment, the antimicrobial fiber comprises a polymer that includes nylon and zinc , zinc oxide and / or zinc pyrithione, the relative viscosity of the polyamide composition ranges from 10 to 100, e.g., from 20 to 100, the fibers having greater than 80% zinc retention as measured by dye bath testing, and the fibers having an average diameter of less than 18 microns.

[0089]

[0102] In yet another embodiment, the antimicrobial fiber is a polymer comprising nylon-6,6. the zinc is provided in the form of zinc oxide, the weight ratio of zinc to phosphorus is at least 2:1, and the fiber is free of Staphylococcus aureus as measured by ISO 20743-13. A reduction of at least 95% of Aureus can be demonstrated, the fibers have greater than 90% zinc retention as measured by dye bath testing, and the antimicrobial fibers have an average diameter of less than 10 microns. Method for forming a nonwoven fiber structure

[0103] As described herein, the antimicrobial nonwoven polyamide structure comprises a formulation It is formed by spinning to form fibers that are arranged to form a structure.

[0090]

[0104] In some embodiments, the present disclosure provides a method for providing permanent antimicrobial properties to nonwoven fibers and The present invention provides a method for providing a structure and fabric made from the polyamide blends described herein. In some aspects, fibers, such as polyamide fibers, are made by spinning the polyamides formed in a melt polymerization process. During the melt polymerization process of the polyamide composition, an aqueous monomer solution, such as a salt solution, is heated under controlled conditions of temperature, time and pressure to evaporate the water and achieve polymerization of the monomers, causing the polymer to melt. During the melt polymerization process, a sufficient amount of zinc, and optionally phosphorus, is used in the aqueous monomer solution to form a polyamide mixture prior to polymerization. The monomers are selected based on the desired polyamide composition. Once the zinc and phosphorus are present in the aqueous monomer solution, the polyamide composition can be polymerized. The polymerized polyamide can then be spun into fibers, for example, by melt, solution, centrifugation or electrospinning.

[0091]

[0105] In some embodiments, the antimicrobial fibers having permanent antimicrobial properties are made of poly The method for preparing the amide composition includes the steps of preparing an aqueous monomer solution, adding less than 2000 ppm, e.g., less than 1500 ppm, less than 1000 ppm, less than 750 ppm, less than 500 ppm, or less than 400 ppm of zinc dispersed in the aqueous monomer solution, and adding less than 2000 ppm, e.g., less than 1500 ppm, less than 1000 ppm, less than 750 ppm, less than 500 ppm, or less than 400 ppm of phosphorus, polymerizing the aqueous monomer solution to form a polymer melt, and spinning the polymer melt to form an antimicrobial fiber. In this embodiment, the polyamide is an antimicrobial fiber. The mido composition includes the resulting aqueous monomer solution after the zinc and phosphorus have been added.

[0092]

[0106] In some embodiments, the method comprises preparing an aqueous monomer solution. The aqueous monomer solution may include an amide monomer. In some embodiments, the concentration of the monomer in the aqueous monomer solution is less than 60 wt%, e.g., less than 58 wt%, less than 56.5 wt%, less than 55 wt%, less than 50 wt%, less than 45 wt%, less than 40 wt%, less than 35 wt%, or less than 30 wt%. In some embodiments, the concentration of the monomer in the aqueous monomer solution is greater than 20 wt%, e.g., greater than 25 wt%, greater than 30 wt%, greater than 35 wt%, greater than 40 wt%, greater than 45 wt%, greater than 50 wt%, greater than 55 wt%, or greater than 58 wt%. In some embodiments, the concentration of the monomer in the aqueous monomer solution ranges from 20 wt% to 60 wt%, e.g., 25 wt% to 58 wt%, 30 wt% to 56.5 wt%, 35 wt% to 55 wt%, 40 wt% to 50 wt%, or 45 wt% to 55 wt%. The balance of the aqueous monomer solution may include water and / or additional additives. In some embodiments, the monomer comprises an amide monomer, i.e., a nylon salt, comprising a diacid and a diamine.

[0093]

[0107] In some embodiments, the aqueous monomer solution is a nylon salt solution. The diamine and diacid salt solution can be formed by mixing water, for example, water, diamine and dicarboxylic acid monomers are mixed to form a salt solution, for example, adipic acid and hexamethylene diamine are mixed with water. In some embodiments, the diacid may be a dicarboxylic acid and may be selected from the group consisting of oxalic acid, malonic acid, succinic acid, glutaric acid, pimelic acid, adipic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecandioic acid, maleic acid, glutaconic acid, traumatic acid, and muconic acid, 1,2- or 1,3-cyclohexanedicarboxylic acid, 1,2- or 1,3-phenyl enediacetic acids, 1,2- or 1,3-cyclohexanediacetic acid, isophthalic acid, terephthalic acid, 4,4'-oxybisbenzoic acid, 4,4-benzophenone dicarboxylic acid, 2,6-napthalene dicarboxylic acid, pt-butylisophthalic acid, and 2,5-furandicarboxylic acid, and mixtures thereof. In some embodiments, the diamine is ethanoldiamine, trimethylenediamine, putrescine, cadaverine, hexamethyelene diamine, diamine), 2-methylpentamethylenediamine, heptamethylenediamine, 2-methylhexamethylenediamine, 3-methylhexamethylenediamine, 2,2-dimethylpentamethylenediamine, octamethylenediamine, 2,5-dimethylhexamethylenediamine, nonamethylenediamine, 2,2,4- and 2,4,4-trimethylhexamethylenediamine, decamethylenediamine, 5-methylnonanediamine, isophoronediamine, undecamethylenediamine, dodecamethylenediamine, 2,2,7,7-tetramethyloctamethylenediamine, bis(p-aminocyclohexyl)methane, bis(aminomethyl)norbornane, C2-C16 aliphatic diamines optionally substituted with one or more C1 to C4 alkyl groups, aliphatic polyether diamines and furandiamines, such as 2,5-bis(aminomethyl)furan, and mixtures thereof.In a preferred embodiment, the diacid is adipic acid and the diamine is hexamethylenediamine which is polymerized to form nylon 6,6.

[0094]

[0108] The concept of producing polyamides from diamines and diacids is similar to other suitable monoamines. It should be understood that the present invention also encompasses the concept of a mer, such as an amino acid or a lactam. Without limiting the scope, examples of amino acids include 6-aminohaxanoic acid, 7-aminoheptanoic acid, 11-aminoundecanoic acid, 12-aminododecanoic acid, 13-aminobutyric acid, 14-aminobutyric acid, 15-aminobutyric acid, 16-aminobutyric acid, 17-aminobutyric acid, 18-aminobutyric acid, 19-aminobutyric acid, 20-aminobutyric acid, 21-aminobutyric acid, 22-aminobutyric acid, 23-aminobutyric acid, 24-aminobutyric acid, 25-aminobutyric acid, 26-aminobutyric acid, 27-aminobutyric acid, 28-aminobutyric acid, 29-aminobutyric acid, 30- decanoic acid or combinations thereof. Without limiting the scope of the disclosure, examples of lactams may include caprolactam, enantholactam, lauryllactam or combinations thereof. A suitable feed for the disclosed process may include a mixture of diamines, diacids, amino acids and lactams.

[0095]

[0109] After the aqueous monomer solution is prepared, zinc is added to form the polyamide composition. In some embodiments, less than 2000 ppm of zinc is dispersed in the aqueous monomer solution. In some aspects, further additives, such as additional antimicrobial agents, are added to the aqueous monomer solution. Optionally, phosphorus is added to the aqueous monomer solution.

[0096]

[0110] In some cases, the polyamide compositions are prepared using conventional melt polymerization processes. In one embodiment, the aqueous monomer solution is heated under controlled conditions of time, temperature and pressure to evaporate the water, achieve polymerization of the monomers, and obtain a polymer melt. In some embodiments, a particular zinc to phosphorus weight ratio can advantageously promote binding of the zinc within the polymer, reducing the thermal degradation of the polymer, and improving its dyeability.

[0097]

[0111] In some embodiments, antimicrobial nylon is prepared by melt polymerization of conventional nylon salts. Typically, nylon salt solutions are prepared under pressure (e.g., 250 psig / 1825×10 3 n / m 2 ) to a temperature of, for example, about 245° C. The water vapor is then released by reducing the pressure to atmospheric pressure while the temperature is increased, for example, to about 270° C. Prior to polymerization, zinc, and optionally phosphorus, are added to the nylon salt solution. The resulting molten nylon is held at this temperature for a period of time to equilibrate before being extruded into fibers. In some embodiments, the process can be carried out in a batch or continuous process.

[0098]

[0112] In some embodiments, during melt polymerization, zinc, e.g., zinc oxide, is added to the monomer aqueous solution. The antimicrobial fibers may include polyamides made by a melt polymerization process and not a masterbatch process. In some embodiments, the resulting fibers have permanent antimicrobial properties. The resulting fibers may be used in applications such as socks, heavy hose, and shoes, for example.

[0099]

[0113] The antimicrobial agent may be added during melt polymerization, for example as a masterbatch, or in the form of a polyamide It can be added to the polyamide as a powder that is added to pellets, and then fibers can be formed from the spinning. The fibers are then formed into nonwoven fabrics.

[0100]

[0114] In some aspects, the antimicrobial nonwoven structure is meltblown. Electrospinning is advantageously less expensive than electrospinning. Meltblowing is a process type that has been developed to form microfibers and nonwoven webs. Until recently, microfibers have been produced by meltblowing. Now, nanofibers can also be formed by meltblowing. Nanofibers are formed by extruding a molten thermoplastic polymeric material or polyamide through a number of small holes. The resulting molten threads or filaments are transferred to a converging high velocity gas stream, which attenuates or stretches the molten polyamide filaments, reducing their diameter. The meltblown nanofibers are then carried by the high velocity gas stream and deposited on a collecting surface or forming wire to form a randomly distributed meltblown nanofiber nonwoven web. The formation of nanofibers and nonwoven webs by meltblowing is well known in the art. See, for example, U.S. Patent Nos. 3,704,198; 3,755,527; 3,849,241; 3,978,185; 4,100,324; and 4,663,220.

[0101]

[0115] One option, "islands in the sea," is a method of mixing at least two polymer components in a single spinning die. This refers to fibers, also known as composite yarns, which are formed by extruding the material from a single fiber.

[0116] As is well known, electrospinning is subject to many fabrication parameters that may limit the spinning of certain materials. These parameters include: the charge of the spinning material and the spinning material solution; the solution delivery (the flow of material, often ejected from a syringe); the charge on the jet; the discharge of the fiber membrane in the collector; the external force from the electric field on the spinning jet; the density of the ejected jet; and the (high) voltage of the electrodes and the geometry of the collector. In contrast, the aforementioned nanofibers and products are advantageously formed without the use of an applied electric field as the primary ejection force required for the electrospinning process. Thus, the polyamide is not charged, nor are any components of the spinning process charged. Importantly, the dangerous high voltages required for the electrospinning process are not required for the processes / products disclosed herein. In some embodiments, the process is a non-electrospinning process and the resulting product is a non-electrospun product produced via a non-electrospinning process.

[0102]

[0117] An embodiment of the present invention for making a nanofiber nonwoven fabric is disclosed in U.S. Pat. 54. This process involves two-phase flow of polymer or polymer solution and pressurized propellant gas (typically air) into a narrow, preferably converging channel. The channel is usually and preferably annular in structure. It is believed that the polymer is sheared by the gas flow in the narrow, preferably converging channel, producing polymeric film layers on both sides of the channel. These polymeric film layers are further sheared into nanofibers by the propellant gas flow. Also here, a moving collection belt can be used, and the basis weight of the nanofiber nonwoven fabric is controlled by adjusting the speed of the belt. The collector distance can also be used to control the fineness of the nanofiber nonwoven fabric. The process is better understood with reference to FIG. 1.

[0103]

[0118] Advantageously, the aforementioned polyamide precursors can be used in a melt spinning process. This results in a significant benefit in production rate, e.g., at least 5% faster, at least 10% faster, at least 20% faster, at least 30% faster, at least 40% faster. The improvement can be observed as an improvement in area per time over a conventional process, e.g., another process that does not use the features described herein. In some cases, the increase in production over a period of time is improved. For example, over a given production time, e.g., 1 hour, the disclosed process produces at least 5% more product, e.g., at least 10% more, at least 20% more, at least 30% more, or at least 40% more product than a conventional process or an electrospun process.

[0104]

[0119] FIG. 1 shows a polyamide feed assembly 110, an air supply 1210, a spinning cylinder, The figure illustrates generally the operation of a system for spinning nanofiber nonwoven fabrics, including a spinning cylinder 130, a collection belt 140, and a take-up reel 150. During operation, a polyamide melt or solution is fed into the spinning cylinder 130, where the melt or solution flows through thin channels in the cylinder with high pressure air, shearing the polyamide into nanofibers. Details are given in the aforementioned U.S. Pat. No. 8,668,854. The throughput rate and basis weight are controlled by the gear pump speed and belt speed. Optionally, functional additives, such as charcoal, copper, etc., may be added with the air feed if desired.

[0105]

[0120] In another configuration of the spinneret used in the system of FIG. 1, the particulate material is The additive may be added using a separate inlet as seen in US Pat. No. 5,808,594.

[0121] Yet another methodology that may be used is to prepare polyamide copolymers as disclosed herein. The nanofiber web is then melt-blowed (Figure 2). Melt-blowing involves extruding the polyamide into a relatively high velocity, typically hot, gas stream. To produce suitable nanofibers, careful selection of orifice and capillary geometry, as well as temperature, is required, as seen in Hassan et al., J Membrane Sci., 427, 336-344, 2013, and Ellison et al., Polymer, 48(11), 3306-3316, 2007, and International Nonwoven Journal, Summer 2003, pg 21-28.

[0106]

[0122] U.S. Patent No. 7,300,272 describes a method for extruding molten material into a laminate. Disclosed is a fiber extrusion pack for forming an array of nanofibers, comprising several split distribution plates arranged such that each split distribution plate forms a layer in the fiber extrusion pack, and features on the split distribution plates form a distribution network that delivers molten material to orifices in the fiber extrusion pack. Each of the split distribution plates includes a set of plate segments with a gap disposed between adjacent plate segments. Adjacent edges of the plate segments are shaped to form a reservoir along the gap, and a sealing plug is disposed in the reservoir to prevent the molten material from leaking out of the gap. The sealing plug can be formed by molten material leaking into the gap, collecting in the reservoir, and solidifying, or by placing a plug material in the reservoir in the pack assembly. This pack can be used to make nanofibers using the meltblowing systems described in the previously mentioned patents.

[0107]

[0123] In one embodiment, a method for preparing an antimicrobial nonwoven polyamide structure is disclosed. The process includes forming a (precursor) polyamide, for example by preparing an aqueous monomer solution (preparation of the monomer solution is well known). During the preparation of the precursor, zinc is added (discussed herein). In some cases, zinc is added to (and dispersed in) the aqueous monomer solution.

[0108]

[0124] Phosphorus may also be added. In some cases, the precursor is polymerized to form a polyamide. The process further includes spinning the polyamide to form an antimicrobial polyamide fiber, and forming the antimicrobial polyamide fiber into an antimicrobial nonwoven structure. In some cases, the polyamide composition is melt spun, spunbonded, electrospun, solution spun, or centrifugally spun.

[0109]

[0125] Advantageously, spinning avoids detrimental fiber formation interruptions that create defects in the web structure. It can be carried out at low die pressures that have been found to reduce or eliminate the need for high pressure die spinning. In some embodiments, spinning can be carried out at die pressures of less than 300 psig, such as less than 275 psig, less than 272 psig, less than 250 psig, less than 240 psig, less than 200 psig, less than 190 psig, less than 175 psig, less than 160 psig, or less than 155 psig. In terms of ranges, spinning can be carried out at die pressures ranging from 10 psig to 300 psig, such as 25 psig to 275 psig, 35 psig to 272 psig, 50 psig to 250 psig, 75 psig to 240 psig, 75 psig to 200 psig, or 90 psig to 155 psig.

[0110]

[0126] In some embodiments, optionally in the structures discussed above, antimicrobial nonwoven fibers A method is disclosed for preparing an antimicrobial polyamide fiber having an antimicrobial composition. The method includes preparing a formulation including a polyamide, zinc dispersed within the polyamide, and less than 2000 ppm phosphorus dispersed within the polyamide. The method includes spinning the formulation to form an antimicrobial polyamide fiber having the composition and properties described herein. The method further includes forming the antimicrobial polyamide fiber into an antimicrobial nonwoven polyamide structure. The spinning is performed at a low die pressure as discussed above.

[0111]

[0127] Fabrics can be made from non-woven fibers. Garments made from these fabrics can be: It is able to withstand normal wear and tear and is free of any coatings, dopes or topical treatments that tend to wear off during knitting and weaving. The process of wear creates dust on the machine and fabric, shortening the useful life of the garment under normal wear and tear and washing. polyamide

[0128] As described herein, the antimicrobial polyamide composition can be used for nonwoven fabrics. As used herein, terminology such as "polyamide composition" refers to compositions containing polyamides, including copolymers, terpolymers, polymer blends, alloys, and derivatives of polyamides. Additionally, as used herein, "polyamide" refers to a polymer having as a component a polymer having a bond between an amino group of one molecule and a carboxylic acid group of another molecule. In some embodiments, the polyamide is the component present in the greatest amount. For example, a polyamide containing 40 wt.% nylon 6, 30 wt.% polyethylene, and 30 wt.% polypropylene is referred to herein as a polyamide since the nylon 6 component is present in the greatest amount. Additionally, a polyamide containing 20 wt.% nylon 6, 20 wt.% nylon 66, 30 wt.% polyethylene, and 30 wt.% polypropylene is also referred to herein as a polyamide since the nylon 6 and nylon 66 components are the components present in the greatest amount overall.

[0112]

[0129] Exemplary polyamides and polyamide compositions are disclosed in Kirk-Othmer, E. 18, pp. 328-371 (Wiley, 1982), the disclosure of which is incorporated by reference.

[0113]

[0130] Briefly, polyamides generally consist of repeating units as an integral part of the main polymer chain. Polyamides are known as compounds containing cyclic amide groups. Linear polyamides are of particular interest and may be formed from the condensation of difunctional monomers. Polyamides are often referred to as nylons. Although they are generally thought of as condensation polymers, polyamides may also be formed by ring-opening polymerization. This method of preparation is particularly important for some polymers in which the monomer is a cyclic lactam, such as nylon 6. Specific polymers and copolymers, and their preparation, can be found in the following patents: U.S. Patent Nos. 4,760,129; 5,504,185; 5,543,495; 5,698,658; 6,011,134; 6,136,947; 6,169,162; 7,138,482; 7,381,788; and 8,759,475.

[0114]

[0131] There are many advantages to using polyamides in commercial applications. Nylon is commonly Nylons are highly resistant to chemicals and heat, resulting in superior performance over other polymers. They are also known to have improved strength, elongation and abrasion resistance compared to other polymers. Nylons are also extremely versatile, allowing for their use in a wide variety of applications.

[0115]

[0132] Polyamides that are particularly preferred for some applications include high temperature nylons (HTN's). The classification is based on Glasscock et al., High Performance Polyamides Fulfill Demanding Requirements for Automotive Thermal Management Components, (DuPont), http: / / www2.dupont.com / Automotive / en_US / assets / downloads / knowledg e%20center / HTN-whitepaper-R8.pdf, available online, June 10, 2016. Such polyamides typically include one or more of the structures found below:

[0116] [ka]

[0117]

[0133] Non-limiting examples of polymers that may be included in polyamides include those having combinations of other polymers. Suitable polyamides include polypropylene and copolymers, polyethylene and copolymers, polyesters, polystyrene, polyurethanes, and combinations thereof. Thermoplastic and biodegradable polymers are also suitable for melt-blowing or melt-spinning into nanofibers of the present disclosure. As discussed herein, the polymers may be melt-spun or melt-blown, preferably by two-phase propellant gas spinning, which involves extruding a liquid form of the polyamide composition through a fiber-forming channel with a pressurized gas. Other processes for forming nonwoven structures may also be used, including spunbonding, solution spinning, and centrifugal spinning.

[0118]

[0134] The nylon nanopolymers described herein, including copolymers and terpolymers The melting point of the fiber product can be between 223° C. and 390° C., such as 223 to 380 or 225° C. to 350° C. Additionally, the melting point can be above that of conventional nylon 66, depending on any additional polymeric materials that are added.

[0119]

[0135] Other polymeric materials that may be used in the antimicrobial nanofiber nonwoven fabrics of the present disclosure include: Addition polymer and condensation polymer materials, such as polyolefins, polyacetals, polyacetals, These include both amides (discussed previously), polyesters, cellulose ethers and esters, polyalkylene sulfides, polyarylene oxides, polysulfones, modified polysulfone polymers and mixtures thereof. Preferred materials falling within these general categories include polyamides, polyethylene, polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polytrimethylene terephthalate (PTT), polypropylene, poly(vinyl chloride), polymethyl methacrylate (and other acrylic resins), polystyrene and their copolymers (including ABA type block copolymers), poly(vinylidene fluoride), poly(vinylidene chloride), polyvinyl alcohol in crosslinked and uncrosslinked forms with various degrees of hydrolysis (87% to 99.5%). Addition polymers tend to be glassy (Tg above room temperature). This is the case with polyvinyl chloride and polymethyl methacrylate, polystyrene polymer compositions or alloys, or with polyvinylidene fluoride and polyvinyl alcohol materials with low crystallinity. The nylon copolymers embodied herein can be made by combining various diamine compounds, various diacid compounds and various cyclic lactam structures in a reaction mixture, then forming a nylon with the monomeric materials randomly positioned in a polyamide structure. For example, a nylon 66-6,10 material is a nylon made from hexamethylene diamine and a C6 and C10 blend of diacids. Nylon 6-66-6,10 is a nylon made by copolymerization of epsilon aminocaproic acid, hexamethylene diamine and a blend of C6 and C10 diacid materials.

[0120]

[0136] For example, some embodiments described in U.S. Pat. No. 5,913,993. In the present invention, a small amount of polyethylene polymer can be blended with a nylon compound used to form a nanofiber nonwoven fabric having desirable properties. The addition of polyethylene to nylon enhances certain properties, such as flexibility. The use of polyethylene also reduces production costs and facilitates further downstream processing, such as bonding to other fabrics or to itself. Improved fabrics can be made by adding a small amount of polyethylene to the nylon feedstock used to produce nanofiber meltblown fabrics. More specifically, the fabric can be produced by forming a blend of polyethylene and nylon 66, extruding the blend in the form of a plurality of continuous filaments, meltblowing the filaments through a die, and depositing the filaments on a collecting surface to form a web.

[0121]

[0137] The polyethylene useful in the process of this embodiment of the present disclosure preferably has a molecular weight of about 5 The polyethylene may have a melt index of between about 0.85 grams / cc and about 1.1 grams / cc, such as between about 0.93 grams / cc and about 0.95 grams / cc. Most preferably, the polyethylene has a melt index of about 150 and a density of about 0.93.

[0122]

[0138] The polyethylene used in the process of this embodiment of the present disclosure is about 0.05% The polyethylene may be added at a concentration of between about 0.05% and about 20%. In a preferred embodiment, the concentration of polyethylene is between about 0.1% and about 1.2%. Most preferably, the polyethylene is present at about 0.5%. The concentration of polyethylene in the fabric produced according to the described method is approximately equal to the percentage of polyethylene added during the manufacturing process. Thus, the percentage of polyethylene in the fabric of this embodiment of the disclosure typically ranges from about 0.05% to about 20%, preferably about 0.5%. Thus, the fabric typically contains between about 80 and about 99.95 weight percent nylon. The filament extrusion step can be carried out at between about 250° C. and about 325° C. Preferably, the temperature range is from about 280° C. to about 315° C., but can be lower if nylon 6 is used. be.

[0123]

[0139] The polyethylene and nylon blends or copolymers may be prepared by any suitable method. The nylon compound can be formed in stages. Typically, the nylon compound is nylon 66, although other polyamides of the nylon family can be used. Also, mixtures of nylons can be used. In one embodiment, polyethylene is blended with a mixture of nylon 6 and nylon 66. The polyethylene and nylon polymers are typically supplied in the form of pellets, chips, flakes, and the like. A desired amount of polyethylene pellets or chips can be blended with nylon pellets or chips in a suitable mixing device, such as a rotary drum tumbler, and the resulting blend can be introduced into the feed hopper of a conventional extruder or into a meltblowing line. Blends or copolymers can also be produced by introducing the appropriate mixture into a continuous polymerization spinning system.

[0124]

[0140] Additionally, different species of common polymers can be blended together. For example: High molecular weight styrene materials can be blended with low molecular weight impact polystyrene. Nylon-6 materials can be blended with nylon copolymers, such as nylon-6;66;6,10 copolymers. Additionally, polyvinyl alcohols exhibiting low degrees of hydrolysis, such as 87% hydrolyzed polyvinyl alcohols, exhibiting between 98 and 99.9% and higher degrees of hydrolysis, can be blended with fully or superhydrolyzed polyvinyl alcohols. All of these materials can be crosslinked using appropriate crosslinking mechanisms upon blending. Nylons can be crosslinked using crosslinkers reactive with the nitrogen atoms in the amide bonds. Polyvinyl alcohol materials can be crosslinked using hydroxyl reactive materials, such as monoaldehydes, such as formaldehyde, urea, melamine-formaldehyde resins and their analogs, boric acid and other inorganic compounds, dialdehydes, diacids, urethanes, epoxies and other known crosslinkers. Crosslinking techniques are well known and are an understood phenomenon in which crosslinking reagents react to form covalent bonds between polymer chains, substantially improving molecular weight, chemical resistance, overall strength and resistance to mechanical degradation.

[0125]

[0141] One preferred mode is to combine a first polymer and a second polymer that have been conditioned or treated at elevated temperatures. A blend of two different polymers (different polymer types, molecular weights, or physical properties) can be reacted and molded into a single chemical species. Preferred materials are chemically reacted into a single polymer species such that differential scanning calorimetry (DSC) analysis reveals a single polymeric material that provides improved stability when exposed to high temperatures, humidity, and difficult operating conditions. Preferred materials for use in blended polymer systems include nylon 6; nylon 66; nylon 6,10; nylon (6-66-6,10) copolymers, and other linear, generally aliphatic nylon compositions.

[0126]

[0142] Suitable polyamides are, for example, 20% nylon 6, 60% nylon 66 and and 20% by weight polyester. The polyamide may comprise a combination of compatible polymers or a combination of incompatible polymers.

[0127]

[0143] In some embodiments, the polyamide may include nylon 6. As for the lower limit, In general, the polyamide may comprise nylon 6 in an amount of at least 0.1 wt.%, e.g., at least 1 wt.%, at least 5 wt.%, at least 10 wt.%, at least 15 wt.%, or at least 20 wt.%. In terms of upper limits, the polyamide may comprise nylon 6 in an amount of 99.9 wt.% or less, 99 wt.% or less, 95 wt.% or less, 90 wt.% or less, 85 wt.% or less, or 80 wt.% or less. In terms of ranges, the polyamide may comprise nylon 6 in an amount of 0.1 to 99.9 wt.%, e.g., 1 to 99 wt.%, 5 to 95 wt.%, 10 to 90 wt.%, 15 to 85 wt.%, or 20 to 80 wt.%.

[0128]

[0144] In some embodiments, the polyamide may include nylon 66. In one embodiment, the polyamide may comprise nylon 66 in an amount of at least 0.1 wt.%, e.g., at least 1 wt.%, at least 5 wt.%, at least 10 wt.%, at least 15 wt.%, or at least 20 wt.%. In terms of upper limits, the polyamide may comprise nylon 66 in an amount of 99.9 wt.% or less, 99 wt.% or less, 95 wt.% or less, 90 wt.% or less, 85 wt.% or less, or 80 wt.% or less. In terms of ranges, the polyamide may comprise nylon 66 in an amount of 0.1 to 99.9 wt.%, e.g., 1 to 99 wt.%, 5 to 95 wt.%, 10 to 90 wt.%, 15 to 85 wt.%, or 20 to 80 wt.%.

[0129]

[0145] In some embodiments, the polyamide may comprise nylon 6I, where I is isoflavone. In terms of lower limits, the polyamide may contain nylon 6I in an amount of at least 0.1 wt.%, e.g., at least 0.5 wt.%, at least 1 wt.%, at least 5 wt.%, at least 7.5 wt.%, or at least 10 wt.%. In terms of upper limits, the polyamide may contain nylon 6I in an amount of 50 wt.% or less, 40 wt.% or less, 35 wt.% or less, 30 wt.% or less, 25 wt.% or less, or 20 wt.% or less. In terms of ranges, the polyamide may contain nylon 6I in an amount of 0.1 to 50 wt.%, e.g., 5 to 40 wt.%, 1 to 35 wt.%, 5 to 30 wt.%, 7.5 to 25 wt.%, or 10 to 20 wt.%.

[0130]

[0146] In some embodiments, the polyamide may include nylon 6T, where T is terephthalate. In terms of lower limits, the polyamide may contain nylon 6T in an amount of at least 0.1 wt.%, e.g., at least 1 wt.%, at least 5 wt.%, at least 10 wt.%, at least 15 wt.%, or at least 20 wt.%. In terms of upper limits, the polyamide may contain nylon 6T in an amount of 50 wt.% or less, 47.5 wt.% or less, 45 wt.% or less, 42.5 wt.% or less, 40 wt.% or less, or 37.5 wt.% or less. In terms of ranges, the polyamide may contain nylon 6T in an amount of 0.1 to 50 wt.%, e.g., 1 to 47.5 wt.%, 5 to 45 wt.%, 10 to 42.5 wt.%, 15 to 40 wt.%, or 20 to 37.5 wt.%.

[0131]

[0147] Block copolymers are also useful in the methods of the present disclosure. With respect to the solvent swelling agent selection is important. The solvent selected ensures that both blocks are soluble in the solvent. An example is ABA (styrene-EP-styrene) or AB (styrene-EP) polymers in methylene chloride solvent. If a component is not soluble in the solvent, it will form a gel. Examples of such block copolymers are Kraton® types of styrene-b-butadiene and styrene-b-hydrogenated butadiene (ethylene propylene), Pebax® types of e-caprolactam-b-ethylene oxide, Sympatex® polyester-b-ethylene oxide, and polyurethanes of ethylene oxide and isocyanates.

[0132]

[0148] Polyvinylidene fluoride, Syndiotactic polystyrene, Vinylidene fluoride Addition polymers such as copolymers of ethylenediaminetetraacetate and hexafluoropropylene, polyvinyl alcohol, polyvinyl acetate, amorphous addition polymers such as poly(acrylonitrile) and its copolymers with acrylic acid and methacrylate, polystyrene, poly(vinyl chloride) and its various copolymers, poly(methyl methacrylate) and its various copolymers are known to be relatively easily solution spun because they are soluble at low pressures and temperatures, and are expected to be melt spun according to the present disclosure as a method of making nanofibers.

[0133]

[0149] In polymer blend alloy formats or in cross-linked chemical bond structures It is quite advantageous to form polymeric compositions containing two or more polymeric materials, which the authors believe improve physical properties by modifying the nature of the polymer, for example by improving polymer chain flexibility or chain mobility, increasing overall molecular weight, and strengthening the polymeric material through network formation.

[0134]

[0150] In one embodiment of this concept, two related polymeric materials are combined for beneficial properties. For example, a high molecular weight polyvinyl chloride can be blended with a low molecular weight polyvinyl chloride. Similarly, a high molecular weight nylon material can be blended with a low molecular weight nylon material.

[0135]

[0151] These polyamides utilize the aforementioned zinc and / or phosphorus additives, It has been surprisingly found that when formed into fabrics, odor control characteristics are obtained. In some cases, conventional polymer resins utilizing polyester polymer resins have been found to harbor and thrive different types of bacteria as compared to nylon ones. For example, micrococcus bacteria have been found to thrive in polyester-based fabrics. Thus, it has been surprisingly found that the use of polyamide-based polymers, specifically nylon-based polymers, together with the aforementioned additives, results in fabrics that demonstrate significantly lower odor levels as compared to similar fabrics utilizing polyester. EXAMPLES

[0136] Examples 1 to 6 and Comparative Examples A to E

[0152] The precursor polyamide compositions were prepared using the components listed in Table 1a. For the zinc oxide samples, a masterbatch of zinc oxide in nylon 6 was blended with nylon 6,6 flake to achieve the desired zinc content. For the zinc stearate samples, zinc stearate was added as a powder onto nylon 6,6 flake and processed through a twin screw extruder to achieve the desired zinc content and distribute the material throughout the polymer. For the copper acetate samples, copper acetate was added to the salt solution to achieve the copper content.

[0137] [Table 1]

[0138]

[0153] The precursor composition was blown into fibers using a conventional meltblowing system. The nonwoven web was then placed on top of a scrim that was in turn placed on a moving belt. The process used an extruder with a high compression screw. The (precursor) polyamide die temperature was approximately 323° C. and air was used as the gas.

[0139]

[0154] As mentioned above, the fibers are spun onto the scrim and used to fabricate the nanofibers of the present invention. ) adds integrity to the fibrous web. The polyamides had the RVs listed in Table 1 (before spinning).

[0140]

[0155] The webs were tested for antimicrobial efficacy (ISO 20743-13:20 13). The results are shown in Table 1b.

[0141] [Table 2]

[0142]

[0156] As shown in Table 1a, the webs that contained the disclosed amounts of zinc were In all cases, the comparative examples demonstrated surprisingly high reductions (after 24 hours), e.g., greater than 99.97% reduction, of both Staphylococcus Aureus and Klebsiella pneumoniae. In contrast, the comparative examples A-E, which used little or no zinc compound (or zinc component), demonstrated less than 95% reduction in Staphylococcus Aureus and less than 98.9% reduction in Klebsiella pneumoniae, and in most cases well below 80%.

[0143]

[0157] In particular, the web was treated with Klebsiella pneumoniae for Comparative Examples A to D. The disclosed webs demonstrated particularly good reduction of C. umoniae, e.g., at least 99.999% (vs. only 98.8% in Comparative Example C, and well below 50% in Comparative Examples A, B, and D). Importantly, the disclosed webs demonstrated superior performance to other metals, e.g., copper in Comparative Example E (99.999+ in Examples 1-6, versus only 31.0% in Comparative Example E).

[0144]

[0158] Log reduction numbers are numbers that are greater than or equal to the upper limit of the reduction percentage, e.g. 99.9%. It is often used in industry as a measure of efficacy to emphasize differentiation at percentage reductions above 0.01.

[0145]

[0159] In terms of microbial growth, the log reduction tells us how effective a product is. The greater the reduction in numbers, the more effective the product is in controlling microbial growth. In some cases, during product efficacy testing, the number of colony forming units (CFU) is counted at the beginning of the test. The reduction is then measured over a predefined period of time, e.g., 24 hours. The difference results between and the test product are then expressed as log reduction.

[0146]

[0160] As shown in Table 1b, Klebsiella pneumoniae In the , the disclosed webs demonstrated log reductions well above 2, e.g., greater than 4.5 in most cases. In contrast, Comparative Examples A-E, including Comparative Example E, which utilized a copper compound as the antimicrobial agent, demonstrated log reductions less than 2, e.g., less than 1.0 in most cases.

[0147]

[0161] Staphylococcus Aureus also performed unexpectedly well. The webs demonstrated at least 99.98% reduction of Staphylococcus Aureus versus Comparative Examples A-D (only 94.5% versus Comparative Example E and well below 80% versus Comparative Examples A-D). Importantly, the disclosed webs demonstrated superior performance to other metals, such as copper in Comparative Example E (99.98+ in Examples 1-6 versus only 94.5% versus Comparative Example E).

[0148]

[0162] Also, the number of disclosed web pages is well over 2, for example 3 in most cases. In contrast, Comparative Examples A-E, including Comparative Example E, which utilized a copper compound as the antimicrobial agent, demonstrated a log reduction of less than 1.5, e.g., less than 1.0 in most cases.

[0149]

[0163] These examples and comparative examples are based on the results of experiments performed against other antimicrobial agents and against control samples. , demonstrating the importance of the disclosed zinc compounds (optionally in the disclosed amounts). Examples 7 and 8, and Comparative Examples F and G

[0164] The nonwoven web is processed using zinc oxide added as a masterbatch. The properties and performance characteristics of some specific samples are shown in Table 2a.

[0150] [Table 3]

[0151]

[0165] Comparative Examples F and G were prepared similarly but without the zinc compound.

[0166] The webs were tested for antimicrobial efficacy (ISO 20743-13:201 3). The results are shown in Table 2b.

[0152] [Table 4]

[0153]

[0167] As shown in Table 2b, the webs containing the disclosed amounts of zinc (Example Examples 7 and 9) unexpectedly demonstrated high reductions (after 24 hours), e.g., greater than 99.990% reduction, of both Staphylococcus Aureus and Klebsiella pneumoniae in all cases. In contrast, Comparative Examples F and G, which did not use a zinc compound (or zinc component), demonstrated less than 50% reduction in Staphylococcus Aureus and less than 99.99% reduction in Klebsiella pneumoniae.

[0154]

[0168] In particular, the web was treated with Klebsiella p neumoniae (only 99.9802% in Comparative Example F and 99.7467 in Comparative Example G).

[0155]

[0169] As shown in Table 2b, Klebsiella pneumoniae At , the disclosed webs demonstrated a log reduction of well over 3.7, such as greater than 4 or even greater than 5. In contrast, Comparative Examples F and G demonstrated a log reduction of less than 4.

[0156]

[0170] Staphylococcus Aureus also performed unexpectedly well. The webs demonstrated at least a 99.990% reduction of Staphylococcus Aureus for Comparative Examples F and G (only 43.68% for Comparative Example F and well under 25% for Comparative Example G).

[0157]

[0171] Also, the disclosed webs exhibit greater than 3.5, e.g., greater than 4, log reductions. In contrast, Comparative Examples F and G demonstrated log reductions of less than 1.5, e.g., less than 1.0 in the majority of cases.

[0158] Examples 1-4 and 6 and Comparative Examples A and C (Reduced Die Pressure)

[0172] In addition to the antimicrobial benefits, the use of zinc in the disclosed amounts improves process efficiency. , for example, have been shown to unexpectedly contribute to reduced die pressure and / or improved RV.

[0159]

[0173] Precursor polyamide compositions of Examples 1-4 and 6, and Comparative Examples A and C The was meltblown into a web as described above. The die pressures used are shown in Table 3. The remaining process parameters were held essentially constant, with Sample A exhibiting only slightly higher throughput.

[0160] [Table 5]

[0161]

[0174] As shown, the use of the disclosed compositions reduces die pressure and / or Or a significant reduction in RV, e.g., below 272 psig, is possible (to achieve a web with the same or similar properties. This is a significant advantage in production, since the lower die pressure can contribute to the elimination or reduction of fiber formation interruptions. In some cases, higher die pressures, e.g., greater than 272 psig, have been found to further interrupt fiber formation, which is detrimental to web quality. The interruption of fiber formation creates defects in the web, which are detrimental to many properties, e.g., filtration efficiency and water repellency performance. As shown, Comparative Examples A and C were produced at higher die pressures, e.g., 272 psig and 605 psig. Webs with the same or similar properties were thus achieved using these higher die pressures. Higher die pressures are also known to contribute to other defects, e.g., fiber interruptions. The use of the disclosed compositions with zinc content allows the process to achieve lower die pressures at higher throughputs, thereby increasing the production rate and productivity of the process.

[0162] Examples 10 and 11 and Comparative Examples HM (Reduced Die Pressure)

[0175] The precursor polyamide compositions of Examples 10 and 11, and Comparative Examples H to M, The compositions were prepared as shown in Table 4. Examples 10 and 11 were prepared using the process described above, with zinc stearate as the zinc compound. Comparative Examples HM were similarly prepared, but without the zinc compound.

[0163]

[0176] These precursor polyamide compositions were meltblown into webs as described above. The die pressures used are also shown in Table 4. The remaining process parameters were held essentially constant.

[0164] [Table 6]

[0165]

[0177] As shown, the use of the disclosed formulations reduces die pressure significantly. Lower die pressures, e.g., below 260 psig, are possible (to achieve webs with the same or similar properties. Comparative Examples H-M were produced at higher die pressures, e.g., above 260 psig, and in most cases well above 350 psig. Webs with the same or similar properties were thus achieved using these higher die pressures. Embodiment

[0178] The following embodiments are contemplated. All combinations of features and embodiments are contemplated. can be.

[0166]

[0179] Embodiment 1: A nonwoven polyamide composition having permanent antimicrobial properties, comprising: 1. A nonwoven polyamide composition comprising a nonwoven polyamide having an average fiber diameter of less than 5 microns, less than 2000 ppm zinc dispersed within the polyamide, and less than 2000 ppm phosphorus, the weight ratio of zinc to phosphorus being at least 1.3:1, or less than 0.64:1.

[0167]

[0180] Embodiment 2: The method of embodiment 1, wherein the weight ratio of zinc to phosphorus is at least 2:1. Form.

[0181] Embodiment 3: The relative viscosity of the polyamide composition is from 10 to 100, for example from 20 to Any one of embodiments 1 and 2 up to 100 embodiments.

[0168]

[0182] Embodiment 4: An embodiment in which the polyamide composition comprises less than 500 ppm zinc. Any one of embodiments 1 to 3.

[0183] Embodiment 5: The polyamide composition comprises a matting agent comprising at least a portion of phosphorus. The embodiment of any one of embodiments 1 to 4, including

[0169]

[0184] Embodiment 6: Any of embodiments 1 to 5, wherein the polyamide composition does not contain phosphorus. or one embodiment.

[0185] Embodiment 7: The zinc is zinc oxide, zinc acetate, zinc ammonium carbonate, adipine The embodiment of any one of the preceding embodiments, wherein the zinc compound is obtained via zinc compounds including zinc ammonium salt, zinc stearate, zinc phenylphosphinate, zinc pyrithione, and / or combinations thereof.

[0170]

[0186] Embodiment 8: The zinc compound is zinc phenylphosphinate and / or phenyl The embodiment of embodiment 7, wherein the zinc phosphate is not zinc phosphate.

[0187] Embodiment 9: Phosphorus is selected from the group consisting of phosphoric acid, benzenephosphinic acid, benzenephosphonic acid, The embodiment of any one of the preceding embodiments, obtained via phosphorus compounds including manganese hypophosphite, sodium hypophosphite, monosodium phosphate, hypophosphorous acid, phosphorous acid and / or combinations thereof.

[0171]

[0188]

[0023] Embodiment 10: A polyamide composition comprising less than 500 ppm zinc, The embodiment of any one of the preceding claims, wherein the resin composition comprises a matting agent comprising at least a portion of phosphorus, and the polymeric resin composition inhibits the growth of greater than 90% of Staphylococcus Aureus as measured by ISO 20743-13.

[0172]

[0189] Embodiment 11: The polyamide comprises nylon and the zinc comprises zinc oxide and / or or zinc pyrithione, and the relative viscosity of the polyamide composition ranges from 10 to 100, such as from 20 to 100.

[0173]

[0190] Embodiment 12: The polyamide comprises nylon-6,6 and the zinc comprises zinc oxide. 12. The embodiment of any one of the preceding claims, wherein the weight ratio of zinc to phosphorus is at least 2:1, and the polyamide composition inhibits the growth of greater than 95% of Staphylococcus Aureus as measured by ISO 20743-13.

[0174]

[0191] Embodiment 13: Silver, tin, copper and gold, as well as alloys, oxides and / or The embodiment of any one of embodiments 1-12, further comprising one or more additional antimicrobial agents, including combinations thereof.

[0175]

[0192] Embodiment 14: Any of embodiments 1 to 13, wherein the melting point of the nonwoven fabric is 225° C. or higher. One embodiment.

[0193] Embodiment 15: The nonwoven polyamide is melt spun, spunbonded, electrospun, solution The embodiment of any one of embodiments 1 to 14, which is spun or centrifugally spun.

[0176]

[0194] Embodiment 16: The non-woven polyamide has an average fiber diameter of 1000 nanometers or less. The embodiment of any one of embodiments 1 to 15, wherein

[0195] Embodiment 17: No more than 20% of the fibers have a diameter greater than 700 nanometers. An embodiment of embodiment 16.

[0177]

[0196] Embodiment 18: The polyamide comprises nylon 66 or nylon 6 / 66. Any one of embodiments 1 to 17.

[0197] Embodiment 19: Any of embodiments 1 to 18, wherein the polyamide comprises high temperature nylon. One embodiment.

[0178]

[0198] Embodiment 20: The polyamide is selected from the group consisting of N6, N66, N6T / 66, N612, N6 The embodiment of any one of the preceding claims, including N6I / 66, N6I / 66, N66 / 6I / 6T, N11 and / or N12, where "N" means nylon.

[0179]

[0199]

[0041] Embodiment 21: A nonwoven polyamide fiberglass ... 2 Air permeability value of less than Any one of embodiments 1 to 20, comprising:

[0200] Embodiment 22: An embodiment in which the nonwoven polyamide has a basis weight of 200 GSM or less. Any one of embodiments 1 to 21.

[0180]

[0201] Embodiment 23: An antimicrobial fiber having permanent antimicrobial properties, comprising 25 microns. 1. An antimicrobial fiber comprising a nonwoven polyamide having an average fiber diameter of less than 1.0 mm, less than 2000 ppm zinc dispersed within the polymer, and less than 2000 ppm phosphorus.

[0181]

[0202] Embodiment 24: The zinc to phosphorus weight ratio is at least 1.3:1, or 0.6 The embodiment of embodiment 23, wherein the ratio is less than 4:1.

[0203] Embodiment 25: The weight ratio of zinc to phosphorus of embodiment 2 is at least 2:1. Any one of 3 or 24 embodiments.

[0182]

[0204] Embodiment 26: The method of embodiment 23, wherein the fibers have an average diameter of less than 20 microns. Any one of the embodiments of to 25.

[0205] Embodiment 27: The polymer of embodiment 23, wherein the polymer comprises less than 2000 ppm zinc. Any one of the embodiments of to 26.

[0183]

[0206] Embodiment 28: The polymer comprises a matting agent comprising at least a portion of phosphorus. Any one of embodiments 23 to 27.

[0207]

[0081] Embodiment 29: The antimicrobial fiber comprises greater than 70% zinc as measured by a dye bath test. The embodiment of any one of embodiments 23 to 28, wherein the retention rate is

[0184]

[0208] Embodiment 30: The zinc is zinc oxide, zinc acetate, zinc ammonium carbonate, adipite Zinc ammonium phosphate, zinc stearate, zinc phenylphosphinate, zinc pyrithione The embodiment of any one of embodiments 23 to 29, wherein the zinc compound comprises:

[0185]

[0209] Embodiment 31: Phosphorus is phosphoric acid, benzenephosphinic acid, benzenephosphonic acid The embodiment of any one of embodiments 23-30, wherein the phosphorus compound is manganese hypophosphite, sodium hypophosphite, monosodium phosphate, hypophosphorous acid, phosphorous acid, and / or combinations thereof.

[0186]

[0210] Embodiment 32: The polyamide comprises less than 500 ppm zinc and the polymer comprises: The embodiment of any one of embodiments 23 to 31, comprising a matting agent comprising at least a portion of phosphorus, wherein the antimicrobial fiber inhibits the growth of greater than 90% of Staphylococcus Aureus as measured by ISO 20743-13.

[0187]

[0211] Embodiment 33: The polyamide comprises nylon and the zinc comprises zinc oxide and / or or zinc pyrithione, the relative viscosity of the polymeric resin composition ranges from 10 to 100, such as from 20 to 100, the antimicrobial fiber having greater than 80% zinc retention as measured by a dye bath test, and the fiber having an average diameter of less than 18 microns.

[0188]

[0212] Embodiment 34: The polyamide comprises nylon-6,6 and the zinc is zinc oxide. and a weight ratio of zinc to phosphorus of at least 2:1, wherein the antimicrobial fiber inhibits greater than 95% growth of Staphylococcus Aureus as measured by ISO 20743-13, the antimicrobial fiber has greater than 90% retention of zinc as measured by a dye bath test, and the antimicrobial fiber has an average diameter of less than 10 microns.

[0189]

[0213] Embodiment 35: The polymer is made of silver, tin, copper and gold, as well as alloys, oxides, etc. The embodiment of any one of embodiments 23-34, further comprising one or more additional antimicrobial agents, including and / or combinations thereof.

[0190]

[0214] Embodiment 36: Any of embodiments 23 to 35, wherein the melting point of the nonwoven fabric is 225° C. or higher. Any one of the embodiments.

[0215] Embodiment 37: The nonwoven polyamide is melt spun, spunbonded, electrospun, solution The embodiment of any one of embodiments 23 to 36, which is spun or centrifugally spun.

[0191]

[0216] Embodiment 38: The nonwoven polyamide has an average fiber diameter of 1000 nanometers or less. The embodiment of any one of embodiments 23 to 37, wherein

[0217] Embodiment 39: No more than 20% of the fibers have a diameter greater than 700 nanometers. An embodiment of embodiment 38.

[0192]

[0218] Embodiment 40: The polyamide comprises nylon 66 or nylon 6 / 66. Any one of embodiments 23 to 39.

[0219] Embodiment 41: Any of embodiments 23 to 40, wherein the polyamide comprises high temperature nylon. Any one of the embodiments.

[0193]

[0220] Embodiment 42: The polyamide is selected from the group consisting of N6, N66, N6T / 66, N612, N6 The embodiment of any one of embodiments 23 to 41, including N6I / 66, N66 / 6I / 6T, N11 and / or N12, wherein "N" means nylon.

[0194]

[0221]

[0046] Embodiment 43: A nonwoven polyamide fiberglass ... 2 Air permeability value of less than The embodiment of any one of embodiments 23 to 42, comprising:

[0222] Embodiment 44: An embodiment in which the nonwoven polyamide has a basis weight of 200 GSM or less. The embodiment of any one of modes 23 to 43.

[0195]

[0223] Example 45: Preparing an antimicrobial nonwoven polyamide with permanent antimicrobial properties 1. A method for producing an antimicrobial polyamide comprising the steps of preparing an aqueous monomer solution that forms a polyamide, adding less than 2000 ppm of zinc dispersed in the aqueous monomer solution, adding less than 2000 ppm of phosphorus, polymerizing the aqueous monomer solution to form a polyamide, spinning the polyamide to form an antimicrobial polyamide fiber, and forming the antimicrobial polyamide fiber into an antimicrobial nonwoven polyamide fiber having a fiber diameter of less than 25 microns, wherein the weight ratio of zinc to phosphorus is at least 1.3:1, or less than 0.64:1.

[0196]

[0224] Embodiment 46: The method of embodiment 45, wherein the polymer comprises less than 2000 ppm of zinc. An embodiment of the present invention.

[0225]

[0081] Embodiment 47: The antimicrobial fiber has greater than 70% zinc as measured by a dye bath test. The embodiment of any one of embodiments 45 or 46, wherein the retention rate is

[0197]

[0226] Embodiment 48: The step of adding phosphorus comprises adding a polish containing at least a portion of the phosphorus. The embodiment of any one of embodiments 45 to 47, comprising adding an eraser.

[0227] Embodiment 49: A polyamide is melted and forced through a die into a high velocity gaseous stream. The embodiment of any one of embodiments 45 to 48, which is melt spun by blowing.

[0198]

[0228]

[0046] Embodiment 50: The polyamide is a polyamide composition in liquid form, which is mixed with a fiber-forming catalyst. The embodiment of any one of embodiments 45 to 49, wherein the melt spun is by two-phase propellant gas spinning, comprising extruding the mixture through a nozzle with a pressurized gas.

[0199]

[0229] Embodiment 51: A nonwoven fabric is formed by collecting fibers on a moving belt. The present invention relates to any one of embodiments 45 to 50.

[0230] Embodiment 52: The relative viscosity of the polyamide in the nonwoven fabric is determined by the spun and nonwoven fabric forms. The embodiment of any one of embodiments 45 to 51, wherein the thermal expansion coefficient is reduced compared to the polyamide prior to polymerization.

[0200]

[0231] Embodiment 53: The relative viscosity of the polyamide in the nonwoven fabric is determined by the spun and nonwoven fabric forms. The embodiment of any one of embodiments 45 to 52, wherein the thermal expansion coefficient is the same or increased compared to the polyamide prior to synthesis.

[0201]

[0232]

[0046] Embodiment 54: A nonwoven fabric comprising nylon 6.0 which is melt spun and formed into said nonwoven fabric. 54. The embodiment of any one of embodiments 45 to 53, wherein the nonwoven fabric comprises a 6 polyamide and has a TDI of at least 20 ppm and an ODI of at least 1 ppm.

[0202]

[0233]

[0046] Embodiment 55: A nonwoven fabric is a nylon fabric that is melt spun into fibers and formed into the nonwoven fabric. The embodiment of any one of embodiments 45 to 54, wherein the fiber comprises LON 66 polyamide and no more than 20% of the fibers have a diameter greater than 25 microns.

[0203]

[0234] Embodiment 56: The polyamide is melt spun, spunbonded, electrospun, solution spun, or centrifugally spun.

[0235] Embodiment 57: A non-woven polyamide structure having antimicrobial properties, comprising: The fibers contain less than 4000 ppm zinc and less than 2000 ppm phosphorus dispersed within the non-woven polyamide fibers, the fibers have an average fiber diameter of less than 25 microns, and the polyamide structure has a Staphylococcus aureus (SAC) content as measured by ISO 20743-13. A non-woven polyamide construction demonstrating at least 90% reduction of C. aureus.

[0204]

[0236] Embodiment 58: The zinc to phosphorus weight ratio is at least 1.3:1, or 0.6 The embodiment of embodiment 57, wherein the ratio is less than 4:1.

[0237] Embodiment 59: The polyamide composition of embodiment 5, wherein the relative viscosity is less than 100 7 or 58 of any one of the embodiments.

[0205]

[0238]

[0041] Embodiment 60: A polyamide composition comprising less than 3100 ppm zinc, The embodiment of any one of embodiments 57-59, wherein the amide composition comprises a matting agent comprising at least a portion of phosphorus, and the polyamide demonstrates at least a 90% reduction in Staphylococcus Aureus as measured by ISO 20743-13.

[0206]

[0239]

[0081] Embodiment 61: The nonwoven polyamide is melt spun, spunbonded, electrospun, solution The embodiment of any one of embodiments 57 to 60, which is spun or centrifugally spun.

[0240] Embodiment 62: No more than 20% of the fibers have a diameter greater than 700 nanometers. Any one of embodiments 57 to 61.

[0207]

[0241] Embodiment 63: The polyamide comprises nylon 66 or nylon 6 / 66. Any one of embodiments 57 to 62.

[0242] Embodiment 64: An antimicrobial fiber having antimicrobial properties, comprising a nonwoven polyamide fiber. 1. An antimicrobial fiber comprising less than 4000 ppm zinc and less than 2000 ppm phosphorus dispersed within the fiber, the fiber having an average fiber diameter of less than 25 microns, and the polyamide structure demonstrating at least a 90% reduction in Staphylococcus Aureus as measured by ISO 20743-13.

[0208]

[0243] Embodiment 65: The zinc to phosphorus weight ratio is at least 1.3:1, or 0.6 The embodiment of embodiment 64, wherein the ratio is less than 4:1.

[0244] Embodiment 66: The method of embodiment 64, wherein the fibers have an average diameter of less than 20 microns. Or any one of 65 embodiments.

[0209]

[0245] Embodiment 67: An embodiment in which the nonwoven polyamide contains less than 3100 ppm zinc. The embodiment of any one of modes 64 to 66.

[0246]

[0081] Embodiment 68: The antimicrobial fiber comprises greater than 70% zinc as measured by a dye bath test. The embodiment of any one of embodiments 64 to 67, wherein the retention rate is

[0210]

[0247] Embodiment 69: A nonwoven polyamide comprising less than 3200 ppm zinc and a polymer The embodiment of any one of embodiments 64-68, wherein the antimicrobial fiber comprises a matting agent comprising at least a portion of phosphorus, and the antimicrobial fiber demonstrates at least a 90% reduction in Staphylococcus Aureus as measured by ISO 20743-13.

[0211]

[0248] Embodiment 70: The nonwoven polyamide is melt spun, spunbonded, electrospun, solution The embodiment of any one of embodiments 64 to 69, which is spun or centrifugally spun.

[0249] Embodiment 71: The polyamide comprises nylon 66 or nylon 6 / 66. Any one of embodiments 64 to 70.

[0212]

[0250] Embodiment 72: Antimicrobial nonwoven polyamide structures having permanent antimicrobial properties are prepared. 1. A method for making an antimicrobial polymer comprising the steps of: preparing a precursor polyamide optionally comprising an aqueous monomer solution; dispersing less than 4000 ppm of zinc in the precursor polyamide; dispersing less than 2000 ppm of phosphorus in the precursor polyamide; polymerizing the precursor polyamide to form a polyamide composition; spinning the polyamide composition to form an antimicrobial polymer. A method comprising forming a biological polyamide fiber and forming the antimicrobial polyamide fiber into an antimicrobial nonwoven structure having a fiber diameter of less than 25 microns.

[0213]

[0251] Embodiment 73: An antimicrobial nonwoven polyamide has a 70% or less viscosity as measured by a dye bath test. % zinc retention.

[0252] Embodiment 74: The zinc to phosphorus weight ratio is at least 1.3:1, or 0.6 The embodiment of any one of embodiments 72 or 73, wherein the ratio is less than 4:1.

[0214]

[0253] Embodiment 75: A polyamide is melted and forced through a die into a high velocity gaseous stream. The embodiment of any one of embodiments 72 to 74, which is melt spun by blowing.

[0254]

[0041] Embodiment 76: A nonwoven fabric is a nylon fabric that is melt spun into fibers and formed into the nonwoven fabric. The embodiment of any one of embodiments 72 to 75, wherein the fiber comprises LON 66 polyamide and no more than 20% of the fibers have a diameter greater than 25 microns.

[0215]

[0255] Embodiment 77: The polyamide is melt spun, spunbonded, electrospun, solution spun, or centrifugally spun.

[0256] Embodiment 78: A non-woven polyamide structure having antimicrobial properties, comprising: 1. A nonwoven polyamide structure comprising: nonwoven polyamide fibers having an average fiber diameter of less than 100 nm; less than 4000 ppm zinc dispersed within the nonwoven polyamide fibers; and wherein the polyamide composition demonstrates at least a 90% reduction in Staphylococcus Aureus as measured by ISO 20743-13.

[0216]

[0257] Embodiment 79: A method for preparing an antimicrobial nonwoven polyamide structure having antimicrobial properties, comprising preparing a formulation comprising a polyamide, less than 4000 ppm zinc dispersed in the polyamide, and less than 2000 ppm phosphorus dispersed in the polyamide, spinning the formulation to form antimicrobial polyamide fibers having a fiber diameter of less than 25 microns, and forming the antimicrobial polyamide fibers into an antimicrobial nonwoven polyamide structure, wherein the fibers are spun using a die pressure of less than 275 psig.

[0258] Although the present invention has been described in detail, modifications within the spirit and scope of the present invention will be readily apparent to those skilled in the art. With regard to the above discussion, relevant knowledge in the art, and references discussed above in connection with the background art and the detailed description of the invention, all of the disclosures thereof are incorporated herein by reference. Furthermore, it should be understood that the embodiments of the present invention, as well as parts of various embodiments, and various features recited below and / or in the appended claims, can be combined or interchanged in whole or in part. In the above description of various embodiments, an embodiment referring to another embodiment can be appropriately combined with other embodiments recognized by those skilled in the art. The present invention includes the following embodiments. (1) An antimicrobial nonwoven polyamide structure comprising: The nonwoven polyamide fiber, Less than 4000 ppm of zinc dispersed within non-woven polyamide fibres; and Contains less than 2000 ppm phosphorus; the fibers have an average fiber diameter of less than 25 microns; A non-woven polyamide structure, wherein the polyamide structure demonstrates at least a 90% reduction in Staphylococcus Aureus as measured by ISO 20743-13. (2) The nonwoven polyamide structure of (1), wherein the weight ratio of zinc to phosphorus is at least 1.3:1, or less than 0.64:1. (3) The nonwoven polyamide structure of (1), wherein the polyamide composition has a relative viscosity of less than 100. (4) The nonwoven polyamide structure of (1), wherein the polyamide composition comprises less than 3100 ppm zinc, the polyamide composition comprises a matting agent comprising at least a portion of phosphorus, and the polyamide demonstrates at least a 90% reduction in Staphylococcus Aureus as measured by ISO 20743-13. (5) The nonwoven polyamide structure of (1), wherein the nonwoven polyamide is melt spun, spunbond, electrospun, solution spun or centrifugally spun. (6) The nonwoven polyamide structure of (1), wherein no more than 20% of the fibers have a diameter greater than 700 nanometers. (7) The nonwoven polyamide structure of (1), wherein the polyamide comprises nylon 66 or nylon 6 / 66. (8) An antimicrobial fiber having antimicrobial properties, Less than 4000 ppm of zinc dispersed within non-woven polyamide fibres; and Contains less than 2000 ppm phosphorus; the fibers have an average fiber diameter of less than 25 microns; An antimicrobial fiber, the polyamide structure demonstrating at least a 90% reduction of Staphylococcus Aureus as measured by ISO 20743-13. (9) The antimicrobial fiber according to (8), wherein the weight ratio of zinc to phosphorus is at least 1.3:1, or less than 0.64:1. (10) The antimicrobial fiber of (8), wherein the fiber has an average diameter of less than 20 microns. (11) The antimicrobial fiber according to (8), wherein the nonwoven polyamide contains less than 3100 ppm of zinc. (12) The antimicrobial fiber according to (8), wherein the antimicrobial fiber has a zinc retention rate of greater than 70% as measured by a dye bath test. (13) The antimicrobial fiber of (8), wherein the nonwoven polyamide contains less than 3200 ppm zinc, the polymer contains a matting agent comprising at least a portion of phosphorus, and the antimicrobial fiber demonstrates at least a 90% reduction in Staphylococcus Aureus as measured by ISO 20743-13. (14) The antimicrobial fiber of (8), wherein the nonwoven polyamide is melt spun, spunbond, electrospun, solution spun, or centrifugally spun. (15) The antimicrobial fiber according to (8), wherein the polyamide comprises nylon 66 or nylon 6 / 66. (16) A method for preparing an antimicrobial nonwoven polyamide structure having permanent antimicrobial properties, comprising: Preparing a precursor polyamide, optionally comprising an aqueous monomer solution; dispersing less than 4000 ppm of zinc in a precursor polyamide; dispersing less than 2000 ppm of phosphorus in a precursor polyamide; polymerizing the precursor polyamide to form a polyamide composition; spinning the polyamide composition to form an antimicrobial polyamide fiber; and A method comprising forming antimicrobial polyamide fibers into an antimicrobial nonwoven structure having a fiber diameter of less than 25 microns. (17) The method of (16), wherein the antimicrobial nonwoven polyamide has greater than 70% zinc retention as measured by a dye bath test. (18) The method according to (16), wherein the weight ratio of zinc to phosphorus is at least 1.3:1, or less than 0.64:1. (19) The method according to (16), wherein the polyamide is melt spun by melt blowing through a die into a high velocity gaseous stream. (20) The method of (16), wherein the nonwoven fabric comprises nylon 66 polyamide that is melt spun into fibers and formed into the nonwoven fabric, and wherein no more than 20% of the fibers have a diameter greater than 25 microns. (21) The method according to (16), wherein the polyamide is melt spun, spunbonded, electrospun, solution spun or centrifugally spun. (22) A nonwoven polyamide structure having antimicrobial properties, non-woven polyamide fibres having an average fibre diameter of less than 25 microns; Contains less than 4000 ppm of zinc dispersed within non-woven polyamide fibres; A nonwoven polyamide structure, wherein the polyamide composition demonstrates at least a 90% reduction in Staphylococcus Aureus as measured by ISO 20743-13. (23) A method for preparing an antimicrobial nonwoven polyamide structure having antimicrobial properties, comprising the steps of: preparing a formulation comprising a polyamide, less than 4000 ppm zinc dispersed within the polyamide, and less than 2000 ppm phosphorus dispersed within the polyamide; spinning the blend to form antimicrobial polyamide fibers having a fiber diameter of less than 25 microns; and forming antimicrobial polyamide fibers into an antimicrobial nonwoven polyamide structure; The process wherein the fibers were spun using a die pressure of less than 275 psig.

Claims

1. 1. A non-woven polyamide structure having antimicrobial properties comprising: The nonwoven polyamide fiber, 200 ppm to 3000 ppm of zinc dispersed within non-woven polyamide fibers, and Contains 0 ppm to 2000 ppm phosphorus; the fibers have an average fiber diameter of less than 25 microns; A non-woven polyamide structure, wherein the polyamide structure demonstrates at least a 90% reduction in Staphylococcus Aureus as measured by ISO 20743-13.

2. The nonwoven polyamide structure of claim 1, wherein the weight ratio of zinc to phosphorus is at least 1.3:1, or less than 0.64:

1.

3. The nonwoven polyamide structure of claim 1, wherein the polyamide composition has a relative viscosity of less than 100.

4. The nonwoven polyamide structure of claim 1, wherein the polyamide composition comprises a matting agent comprising at least a portion of phosphorus, and the polyamide structure demonstrates at least a 90% reduction in Staphylococcus Aureus as measured by ISO 20743-13.

5. The nonwoven polyamide structure of claim 1, wherein the nonwoven polyamide is melt spun, spunbonded, electrospun, solution spun or centrifugally spun.

6. The nonwoven polyamide structure of claim 1, wherein the polyamide comprises nylon 66 or nylon 6 / 66.

Citation Information

Patent Citations

  • Articles with antibacterial and antifungal activity

    CN1729318A

  • JP1972001712B

  • Battery separator and its manufacture

    JP1998326607A

  • Antibacterial cloth

    JP2002242044A

  • Antibacterial polyamide fiber having excellent resistance to washing, antibacterial polyamide crimped textured yarn, antibacterial polyamide woven or knitted fabric and method for producing antibacterial polyamide fiber

    JP2002249925A